Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Unveiling the role of heat shock protein 83 (HSP83) in Gossypium hirsutum in enhancing whitefly stress tolerance - Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Ifrah Imran; Mohammad Abubakar Yasin; Mariam Akhtar; Imran Amin (Molecular Genetics and Genomics, 2026)

CRISPR–cas systems in pharmacology: functional pharmacogenomics, drug screening, resistance, and therapeutic translation - Muhammad Saeed Akhtar; Adnan Amin (Functional & Integrative Genomics, 2026)

Transgene-free plant genome editing via viral delivery of miniature CRISPR-Cas12f - Muhammad Jawad Akbar Awan; Afzal Akram; Rubab Zahra Naqvi; Mariam Akhtar; Saqib Siddique; Muhammad Ismail Buzdar; Imran Amin; Shahid Mansoor (Functional & Integrative Genomics, 2026)

Seasonal fluctuation of airborne bacterial dynamics and disinfectant resistance in hospital environment - Shabana Bano; Imran Hashmi; Muhammad Akhtar Khan; Aiza Javed; Nazish Iftikhar (Aerobiologia, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Nano-formulated β-glucans from Saccharomyces cerevisiae enhance immunity and protection against coccidiosis in broiler chickens - Muhammad Noor; Muhammad Irfan Anwar; Mian Muhammad Awais; Masood Akhtar; Faqir Muhammad (Veterinary Parasitology, 2026)

Portable metagenomics for preventive surveillance and outbreak control in livestock and poultry: Pathogen detection, resistome profiling, and antimicrobial stewardship - Muhammad Saeed Akhtar; Wajid Zaman (Research in Veterinary Science, 2026)

Artificial intelligence-driven metallogenic typing of pyrite from global ore systems - Muhammad Amar Gul; Asia Kanwal; Mohamed Faisal; Tehseen Zafar; Rizwan Sarwar Awan; Shamim Akhtar; Ibrar Khan; Xiaoyong Yang (Journal of Geochemical Exploration, 2026)

Performance prediction of multi-effect desalination (MED) plant: Experimental evaluation, machine learning modelling and optimization - Uzair Ahmad; Muhammad Ahmad Jamil; Muhammad Wakil Shahzad; Faheem Hassan Akhtar (Desalination, 2026)

Kollidon® SR–Stearic Acid Based Thermoresponsive Solid Lipid Nanoparticles for Dual Cisplatin–Epirubicin Delivery: Formulation Development and In-Vitro Evaluation - Farrukh Mehmood; Muhammad Imran Khan; Zulcaif Ahmad; Muhammad Furqan Akhtar; Fareeha Anwar; Tassawer-e-Meran (Journal of Pharmaceutical Innovation, 2026)

Integrated experimental and computational insights into co-production of pectinase and xylanase from Aspergillus niger: Optimization, purification and molecular characterization - Nayya Waseem Dar; Muhammad Anjum Zia; Muhammad Shahid; Bushra Akhtar (Bioresource Technology Reports, 2026)

Correction to: Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

The rise of MXene: A new paradigm in 2D materials for energy storage devices - Muhammad Kaleem Shabbir; Javeed Akhtar; Fozia Arif; Haleema Asghar; Imamdin Chandio; Hafsa Khurshid; Khalid Hussain Thebo; Mohamed H. Helal (Journal of Environmental Chemical Engineering, 2026)

Biochar-amended soil and foliar-applied TiO2 nanoparticles: Mechanistic insights into chromium stress mitigation in rice - Muhammad Waseem; Saqib Ali; Muhammad Saim Talal; Tayyaba Akhtar (Biocatalysis and Agricultural Biotechnology, 2026)

Therapeutic evaluation of myricetin in experimental arthritis: modulation of inflammatory signaling and oxidative stress pathways - Iqra Ijaz; Tasleem Akhtar; Usman aftab; Nadia Naseem; Muhammad Shahzad; Haleema Sohail; Sumetha Yaseen (Inflammopharmacology, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

Use selenium-doped TiO2 single-wall carbon nanotubes as promoter of biochemical indices in Solanum lycopersicum L. under bacterial wilt stress conditions - Asif Kamal; Akhtar Munir; Khizar Hayat Khan; Ulfat Ara; SK Safdar Hossain; Abdulrazak J. Otaru; Muhammad Tahir Amin; Hayat Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nickel and Cobalt Accumulation and Human Health Risk in Guava (Psidium guajava L.) Under Wastewater Irrigation: A Soil–Plant Transfer Assessment - Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Sana Anwar; Shahzad Akhtar; Ijaz Rasool Noorka; Muhammad Irfan Ashraf; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Species composition, relative abundance and seasonal variation of medically important mosquitoes in district Bajaur, Khyber Pakhtunkhwa, Pakistan - Halimullah; Waleeja Tur Rabbia; Naveeda Akhtar Qureshi; Waheed Ali Panhwar; Sajid Malik; Muhammad Ilyas (Acta Parasitologica, 2026)

Genome‐Guided Dissection of ser and shlB Uncovers Multifactorial Virulence Mechanisms of Serratia marcescens PXG6 in Plutella xylostella - Muhammad Rehan Akhtar; Jun Ma; Yan Sun; Xiaofeng Xia (Environmental Microbiology, 2026)
The rapid evolution of pesticide resistance in Plutella xylostella has reduced the effectiveness of conventional pest control methods in cruciferous crops. This study investigated the virulence of Serratia marcescens PXG6 against P. xylostella and identified two putative virulence factors, ser (serralysin) and shlB (hemolysin transporter). Whole‐genome sequencing revealed a GC content of 59.65%, 4650 predicted genes, multiple secretion systems (types I, V, and VI), and 715 putative virulence‐related genes. Bioinformatic analyses predicted type IV pili, serralysin, hemolysin, and flagella as pathogenic determinants. Purified prodigiosin exhibited concentration‐dependent insecticidal activity, whereas bacterial proteins alone caused little larval mortality, indicating that full virulence depends on live bacterial cells. Gene knockout mutants Δ ser and Δ shlB exhibited altered growth, motility, biofilm formation, and stress tolerance. Deletion of shlB significantly reduced hemolytic activity, protein secretion, and virulence against P. xylostella , whereas Δ ser had minimal impact on larval survival. Overall, PXG6 pathogenicity involves multiple bacterial components, with shlB playing a key role in virulence. These findings improve our understanding of the pathogenic mechanisms of PXG6 and support the development of S. marcescens ‐based biocontrol strategies against P. xylostella .

Spatially resolved estimates of phytoplankton carbon fixation and diffusive methane flux potential in a subtropical reservoir - Sheraz Akhtar Gil; YuPing Su; Gohar Ayub; Abdul Samad; Muhammad Irfan Ahamad; Jehangir Ijaz; Shiyu Huang; Weng Yuxin (Environmental Monitoring and Assessment, 2026)

Retraction Note: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2026)

Lactobacilli Mitigate Gut Inflammation by Modulating T-Helper/T-Regulatory Cells and Suppressing Signaling Pathways in Food-Derived Models - Md. F. Kulyar; Syed Umair Ali Shah Naqvi; Eiva Bernotiene; Muhammad Akhtar (Probiotics and Antimicrobial Proteins, 2026)
Intestinal inflammation disrupts epithelial integrity, fuels antibiotic resistance, and underlies disorders such as inflammatory bowel disease. Lactobacillus species, established inhabitants of traditional and contemporary fermented foods, are increasingly viewed as bioactive cultures that shape host immunity and support formulation of next-generation functional foods. This review integrates multidisciplinary evidence from in vitro studies, animal models, human observations, and multi omics datasets to clarify how dietary or probiotic Lactobacillus strains alleviate gut inflammation. Particular attention is given to strain specific effects on T-helper/T-regulatory cell balance, suppression of TLR4-MyD88, NF-κB, MAPK, and NLRP3 signaling cascades, and the influence of food matrices, microencapsulation, dosage, and processing parameters on bacterial viability and efficacy, which are the factors central to food industry application. Across models, Lactobacillus consistently down regulates pro-inflammatory Th1/Th17 responses, while expanding forkhead box protein 3 (Foxp3⁺) T reg, leading to reduced TNF-α, IL-1β, and IL-6 and elevated IL-10 and TGF-β. Short chain fatty acids (SCFAs) and indole metabolites derived from fermentation further dampen NF-κB activity and reinforce epithelial barrier function. Food matrix studies show that dairy and cereal formulations enhance probiotic survival, whereas acidic beverages often require micro encapsulation; a daily intake of ~ 10 10 CFU appears both effective and safe. Taken together, these insights position Lactobacillus as a scientifically robust, industry ready tool for developing anti-inflammatory foods, prioritizing future work for well-designed human feeding trials that couple multi-omics read outs and optimizing strain matrix combinations.

Food security dynamics in South Asia: a multi-method analysis using Random Forest and Error Trend Seasonal models - Muhammad Atiq-ur-Rehman; Sadia Mustafa; Ayesha Hussain; Irfan Hussain Khan; Fatima Akhtar; Sadaf Javed; Azma Batool (Environment, Development and Sustainability, 2026)

Environmental pharmaceutical and antibiotic mixtures: An exposomics-guided framework for mechanistic toxicology - Muhammad Saeed Akhtar; Wajid Zaman (Toxicology Letters, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Field portable Cr2O3 nanozyme based paper sensors for on-site screening of arsenic and cadmium in quality control of herbal products - Fatima Yaseen; Muhammad Faizan; Ali Turab Jafry; Awn Muhammad; Akhtar Hayat; Huma Ajab (Food Bioscience, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pressmud Enhances Soil Microbial Activity, Root Endophyte Populations, Nutrient Uptake, and Wheat Growth in an Antibiotic-Contaminated Soil - Waqar Ul Abbas; Muhammad Imran; Muhammad Akhtar; Basit Haider; Hadeeqa Arshad; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2026)

Roadside dust as a vector of potentially toxic metals: an ecological and human health risk assessment in urban areas of semi-arid climatic regions - Namoos Khan; Kainat Zarin; Muhammad Adnan; Seemab Akhtar; Irfan Ullah; Javed Nawab; Nadeem Ali (Environmental Monitoring and Assessment, 2026)

Synergistic Effects of Crop Residue Incorporation and Sesbania Green Manuring on Nitrogen Release, Ammonia Emission and Wheat Productivity in Rice-Wheat Cropping System - Hafiza Hafsa Iqbal; Sajid Mahmood; Abdul Rasul Awan; Muhammad Akhtar (Journal of Soil Science and Plant Nutrition, 2026)

Influence of weather patterns on ground-level ozone pollution: a 2023 summer case study in Jilin City with health risk assessment - Anees Akhtar; Chunsheng Fang; Ju Wang; Sarfraz Ahmed; Muhammad Awais Haider; Haider Ali; Muhammad Naveed; Samama Tariq (Environmental Monitoring and Assessment, 2026)

Multi-index remote sensing and GIS-based assessment of Shisper Glacier surge dynamics and glacial lake outburst flood hazard in Hunza, Pakistan - Maida Khanum; Yuping Su; Shakeel Mahmood; Kanwal Javid; Jehangir Ijaz; Sheraz Akhtar Gil; Muhammad Irfan Ahamad; Rana Muhammad Zulqarnain (Environmental Monitoring and Assessment, 2026)

Protective effects of linagliptin and tenofovir disoproxil fumarate against APAP-induced acute liver injury: A biochemical, histological, and computational study - Mahnoor Yamin; Muhammad Ali; Arifa Mehreen; Bushra Akhtar; Mansour Abdulaziz Alsaleem; Salim Jamil; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Multimodal bioactivities and COX-2 targeted anti-inflammatory mechanism of enzyme-assisted ultrasonic extracted capsicum and zingiber oleoresins: An integrated computational and experimental study - Muhammad Adeel Razzaq; Muhammad Shahid; Zahid Mushtaq; Bushra Akhtar (Food Bioscience, 2026)

Biopolymer Coated Urea Improves Wheat Productivity and Nitrogen Use Efficiency by Optimizing Plant Physiology and Mineral Acquisition - Wisha Khan; Muhammad Akhtar; Abdul Rasool Awan; Wajid Mahboob; Nadeem Sarwar (Journal of Soil Science and Plant Nutrition, 2026)

Fabrication and In-Vitro and In-Vivo Assessment of Levofloxacin Beads Loaded Floating Tablets to improve Gastric Residence Time - Muhammad Israr; Kamran Ahmad Khan; Ashfaq Ahmad; Kifayat Ullah Shah; Naveed Ullah; Naheed Akhtar (Journal of Pharmaceutical Innovation, 2026)

Kaempferol-loaded solid lipid nanoparticles attenuate cartilage degradation and inflammation by modulating the expression of pro and inflammatory cytokines, MMP-13 and oxidative stress markers in adjuvant induced arthritic rats - Anam Niamat; Aftab Ahmad; Nayla Munawar; Muhammad Shahid; Bushra Akhtar (Inflammopharmacology, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Integrated hydrochemical and health-risk assessment of fluoride and major ions in groundwater from hattar and gadoon industrial estates, pakistan - Tofeeq Ahmad; Anwar Qadir; Muhammad Azam Khan; Nabeel Akhtar; Alaa Ahmed (Environmental Geochemistry and Health, 2026)

Disruption of lipid metabolism under plastic siege: Unraveling the toxic mechanisms of microplastics and nanoplastics - Muhammad Furqan Akhtar; Ammara Saleem (Toxicology and Environmental Health Sciences, 2026)

First report of Steneotarsonemus spinki Smiley (Trombidiformes: Tarsonemidae) infesting greenhouse-grown rice (Oryza sativa L. ssp. indica cv. MR 297) in Malaysia - Noriha Mat Amin; Munirah Tharek; Suhana Yusof; Amin Asyraf Tamizi; Maisarah Mohamad Saad; Siti Akhtar Mohshim; Azlinda Erny Yunus; Muhammad Zamharir Ahmad (Australasian Plant Pathology, 2026)

Boundary-Consistent Ordinal Regression for wheat yield prediction using UAV-based multispectral time-series data - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Muhammad Kashif Naeem; Kanat Yermekbayev; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2026)

Subsidies and international oversight for carbon neutrality in the maritime sector - Wenyue Wu; Ye Yao; Muhammad Akhtar (Transportation Research Part D: Transport and Environment, 2026)

The Ability of Probiotic Strain Escherichia coli O83:K24:H31 to Modulate Gut Homeostasis and Immune Function After Antibiotic-Induced Dysbiosis - Eliška Miková; Eliška Krčmářová; Viktor Černý; Lydie Sklenářová; Pavla Avramová; Eliška Protivová; Barbora Slunéčková; Muhammad Akhtar; Jan Věcek; Jan Procházka; Agnieszka Kubik-Zahorodna; Petra Petrásková; et al. (Probiotics and Antimicrobial Proteins, 2026)
A healthy microbiome and a homeostatic interaction between the microbiome and the host immune system are essential for proper nutrition and overall health. Excessive use of antibiotics (ATB) can disrupt the healthy gut microenvironment, leading to dysbiosis, a condition linked to a wide range of disorders and diseases. Alterations in the composition and function of the microbiota have been associated with a broad spectrum of pathological conditions. In this work, we investigated the effect of ATB administration on microbiota composition and immune modulation, with a particular focus on neutrophil dynamics. We evaluated the capacity of the probiotic strain Escherichia coli O83:K24:H31 (EcO83) to mitigate ATB-induced dysbiosis and restore immune function. As expected, ATB treatment reduced microbiota diversity, which was partially restored by EcO83 supplementation. Furthermore, ATB administration affected the expression of tight junction proteins in the small intestine, an effect reversed by EcO83 treatment. Notably, our data indicate that ATB-induced dysbiosis accelerates neutrophil aging and reduces the release of neutrophils from the bone marrow. EcO83 supplementation counteracts these effects by promoting the influx of newly generated neutrophils into circulation. Overall, our findings confirm that ATB treatment disrupts gut microbiota homeostasis, adversely affecting immune function, including neutrophil turnover. However, probiotic supplementation with EcO83 can at least partially restore microbiome composition and immune homeostasis, highlighting its potential therapeutic application in mitigating ATB-induced dysbiosis.

Amelioration of experimentally induced-arthritis by guaiazulene through targeting inflammatory and oxidative stress biomarkers in Wistar rat - Ammara Saleem; Arooj Fatima; Muhammad Furqan Akhtar (Inflammopharmacology, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

α-Pinene alleviates inflammatory responses and oxidative stress in freund’s complete adjuvant induced arthritic rat model and associated risk factors of atherosclerosis - Khadija Ali; Iqral; Ali Sharif; Bushra Akhtar; Ayesha Younas; Muhammad Ali; Muhammad Furqan Akhtar; Muhammad Imran Khan; Ahmed Al-Harrasi; Aftab Ahmad (Inflammopharmacology, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

Immobilization and stabilization nexus of bio-waste derived biochar towards potentially toxic elements in vegetables: A deterministic and probabilistic human health risk assessment - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Biomass and Bioenergy, 2026)

The ameliorative effects of glutamic acid-capped hydroxyapatite nanoparticles on the physio-chemical parameters of sunflower (Helianthus annuus L.) under induced salt stress - Seemab Akhtar; Irfan Ullah; Muhammad Adnan; Javed Nawab; Rehman Ullah (Journal of Crop Science and Biotechnology, 2026)

Hydroxytyrosol-encapsulated solid lipid nanoparticles mitigate induced arthritis via modulating the cytokines and MMP-13 expression and downregulating oxidative stress in rats - Noor ul Huda; Aftab Ahmad; Muhammad Anjum Zia; Bushra Akhtar (Inflammopharmacology, 2026)

Advancements in predicting bearing capacity of foundations near slopes: a comparative review of LEM/LAM/FEM to AI-driven models - Muhammad Rizwan; Sobia Naseem; Muhammad Akhtar Tarar (Bulletin of Engineering Geology and the Environment, 2026)

Exploring the Role of Mitochondrial Sirtuin 3 Gene in Gastric Cancer Risk Based on SNP Analysis and LORD-Q Assay - Ishrat Mahjabeen; Muhammad Zahid Hussain; Maria Fazal-Ul Haq; Azhar Mehmood; Muhammad Shahbaz Haris; Shereen Ali Khan; Anum Chaudhry; Farzana Hakim; Ayesha Zulfiqar Abbasi; Mahmood Akhtar Kayani (Biochemical Genetics, 2026)

Deciphering water scarcity footprint of auxiliary paddy irrigation via Available Water Remaining (AWARE)-LCA model for sustainable groundwater infrastructure - Naseem Akhtar; Abdulghani Essyah Musbah Swesi; Syahidah Akmal Muhammad; Muhammad Izzuddin Syakir; Raed Sameeh Raja Hussain; Pahmi Husain; Ateyah Alzahrani; Anwar Ulla Khan; Ahmad Alghamdi (Environmental Monitoring and Assessment, 2026)

Postbiotics and Parabiotics: A Viable Health Promoting Alternative for Poultry Industry—A Comprehensive Review - Zhengtian Li; Sikandar Ali; Muhammad Asif Arain; Faiz-ul Hassan; Fazul Nabi; Muhammad Uzair Akhtar; Hemei Yuan (Probiotics and Antimicrobial Proteins, 2026)

Biochemical signatures shaping tissue culture success in maize inbred lines - Rimsha Akhtar; Kauser A. Malik; Umer Zeeshan Ijaz; Asma Maqbool; Zohab Asif; Muhammad Irfan (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Advancing Spatiotemporal Orthophoto Registration in UAV-based Crop Breeding Experiments Leveraging Field Geometric Features - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Haris Khurshid; M. R. Naseem; Karsten Berns; Muhammad Moazam Fraz (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2026)

Calotropis Leaf Extract-Assisted Phytoextraction of Nickel Contaminated Soils - Muhammad Rizwan Shah; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Asif Shehzad; Amjad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Biopolymer Coated Urea Modulates Growth, Physiological and Biochemical Attributes of Maize (Zea Mays L.) Under Drought by Improving Nitrogen and Carbon Acquisition - Nadeem Sarwar; Muhammad Akhtar; Yaosheng Wang (Journal of Soil Science and Plant Nutrition, 2026)

Retraction Note: Esculin-loaded nanoparticles ameliorate adjuvant-induced polyarthritis via subduing inflammatory and oxidative stress biomarkers in Wistar rats - Mehak Fatima; Ammara Saleem; Muhammad Furqan Akhtar; Kanwal Akhtar; Muhammad Imran Khan (Inflammopharmacology, 2026)

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

Environmental persistent free radicals mediated reactive oxygen species generation and oxidative stress responses in soil microbial communities: A review - Sadam Khan; Muhammad Riaz; Shoaib Akhtar; Yuanren Jiang; Chenghe Yan; Kecheng Zhu; Hanzhong Jia (Applied Soil Ecology, 2026)

Validation and pharmacological evaluation of bioactive constituents from Silybum marianum seeds (milk thistle) using in vitro and in silico approaches - Muhammad Tahir Akhtar; Uzma Altaf; Taleeha Roheen; Tahira Almas; Rahman Qadir; Mubshara Saadia (In Silico Pharmacology, 2026)

Optimizing maize straw return enhances wheat yield and nitrogen use efficiency while reducing N2O emissions - Liuge Wu; Qiang Wang; Yuxiao Su; Yuntan Zheng; Yulun Lu; Shanchao Zheng; Muhammad Akhtar; Aixing Deng; Xin Zhang; Zhenwei Song; Chengyan Zheng; Weijian Zhang (Soil and Tillage Research, 2026)

Soil-structure interaction and uplift bearing capacity: A study on low-header CEP single pile foundations - Muhammad Rizwan; Sobia Naseem; Muhammad Akhtar Tarar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

From micro-pixels to macro-performance: An explainable machine learning framework for xanthan gum-stabilized expansive soils via AI-assisted trainable weka segmentation - Muhammad Hamza; Wen-Bo Chen; Jing-Cheng Teng; Han-Jiang Lai; Akhtar Rehman; Muhammad Israr Khan (Journal of Cleaner Production, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

High Adsorption Potential of Co-Pyrolyzed Biochars for Acid Blue 93 in Wastewater - Dania Majeed; Muhammad Bilal Shakoor; Muhammad Awais; Naeem Akhtar Abbasi (Water, Air, & Soil Pollution, 2026)

Curative potential of resveratrol and pterostilbene against epoxy resin–induced reproductive toxicity in female rats - Sidra Malik; Ammara Saleem; Qurat-Ul-Ain; Muhammad Imran Khan; Zulcaif Ahmad; Syeda Momna Ishtiaq; Muhammad Furqan Akhtar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Relation of aflatoxin M1 contamination with milk production, health, and reproductive performance of commercial dairy herds in Punjab, Pakistan - Talat Naseer Pasha; Muhammad Uzair Akhtar; Muhammad Naveed ul Haque (Mycotoxin Research, 2026)

Spatiotemporal dynamics of a reaction-diffusion nutrient-algae model - Muhammad Waqas Yasin; Mobeen Akhtar; Moutaz Alazab; Mustafa Inc; Zafarullah Baber; Muhammad Sajid Iqbal; Shahram Rezapour (Modeling Earth Systems and Environment, 2026)

Formulation and characterization of escin loaded-chitosan nanoparticles and assessment of its anti-arthritic potential in Wistar rats: a mechanistic approach - Ayesha Riaz; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2026)

Classification of clay bricks using vision-based machine learning algorithms - Muhammad Faizan; Muhammad Salman; Muhammad Noman; Ali Akhtar; Afaq Ahmad; Matiullah Bakhtyar (Innovative Infrastructure Solutions, 2026)

Eco-Friendly Gum Arabic–Essential Oil Coatings for Decay Control and Quality Preservation of Pomegranate Fruit During Storage - Muhammad Waqar Alam; Sumreen Anjum; Mubeen Sarwar; Adnan Mukhtar; Akhtar Hameed; Tanveer Hussain; Tauhid Iqbal (Applied Fruit Science, 2026)

Evaluation of resistance level of exotic cotton Gossypium hirsutum accession “Mac-07” against cotton leaf curl disease complex - Khalid Pervaiz Akhtar; Sajawal Iqbal; Najeeb Ullah; Muhammad Qasim Aslam; Muhammad Kashif Riaz Khan; Imran Amin (Journal of Plant Pathology, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Synergistic effect of prednisolone and omega-3 fatty acids revealed through in silico, in vitro, and in vivo approaches against APAP-induced mouse model of acute liver injury - Zainab Rehman; Muhammad Ali; Arifa Mehreen; Ghulam Mustafa; Bushra Akhtar; Ali Sharif; Sehrish Murtaza; Muhammd Haroon Hamed; Amina Sagheer; Mahnoor Yamin (Toxicology and Applied Pharmacology, 2026)

Copper homeostasis: Crosstalk with plant secondary metabolism and stress responses - Muhammad Tanveer Akhtar; Zhaogeng Lu; Shi-xiong Ren; He-lin Zou; Iqra Noor; Biao Jin (Plant Science, 2026)

The role of personal, familial, and institutional factors on Gen Z's behavioral intentions toward food waste prevention - Muhammad Mehedi Masud; K. M. Anwarul Islam; Md. Fakhrudoza Bari; Abdul Alim Baser; Rulia Akhtar; Abdullah Al- Mamun (Environmental Development, 2026)

pH-responsive MIL-101(Fe)/NiFe-LDH composite membranes for high-flux removal of cationic and anionic dyes in wastewater treatment - Shehriyar; Arslan Khurram; Abdul Jabbar; Muhammad Asim Khan; Wenhao Liu; Sadaf Mutahir; Akhtar Munir; Sameerah I. Al-Saeedi (Desalination, 2026)

Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Unlocking geothermal potential in abandoned hydrocarbon and exploration wells: a sustainable energy solution - Muhammad Affan Uddin Ali Khan; Syed Imran Ali; Shaine Muhammadali Lalji; Aliza Hussain; Wajih Hasan; Munira Akhtar Khan; Syed Danish Rasool (Arabian Journal of Geosciences, 2026)

Amino acid functionalized graphene oxide nanocomposite with enhanced adsorption capacity towards methyl orange dye: Insights into kinetics and mechanism - Uzaira Jameel; Muhammad Naveed Qasim; Afnan Qabil Alshammari; Naseem Ahmad Khan; Muhammad Mateen; Behzodjon D. Mamatkodirov; Bakhtiyar T. Ibragimov; Xusheng Wang; Muhammad Nadeem Akhtar (Journal of Water Process Engineering, 2025)

Experimental study of the effects of oxygen enrichment on the stability of a low-swirl biogas non-premixed flame - Sean Fabbro; Muhammad Saqib Akhtar; Madjid Birouk; Janusz A. Kozinski (Fuel, 2025)

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

Manure-enriched Acidic Phosphate Fertilizer Improves Paddy Yield Over the Conventional Phosphate Fertilizers on a Calcisol - Ayesha Siddique; Muhammad Akhtar; Muhammad Saleem; Tahir Hussain Awan; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2025)

Unveiling the Potential of Garcinia Atroviridis Root-Derived Phenolic Compounds Against Breast Cancer: Isolation, Network Pharmacology and In-Silico Approaches - Nur Salsabila Binti Ahmad Roslan; Miah Roney; Abdul Rashid Issahaku; Md. Nazim Uddin; Mohd Fadhlizil Fasihi Mohd Aluwi; Seema Zareen; Anke Wilhelm; Ahmad Mahfuz Gazali; Muhammad Nadeem Akhtar; Normaiza Binti Zamri (Journal of Pharmaceutical Innovation, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Exploring asymmetric effects of blue economy sectors on economic growth: evidence from a non-linear ARDL analysis - Muhammad Mehedi Masud; K. M. Anwarul Islam; Rulia Akhtar; Abdullah Al-Mamun (Aquaculture International, 2025)

Fluorescence spectroscopy as a tool for differentiating methicillin resistance in clinical isolates of Staphylococcus aureus - Rabia Anjum; Sana Imtiaz; Tahseen Rafaqat; Naeem Akhtar; Muhammad Saleem; Muhammad Umar (Journal of Fluorescence, 2025)

Chitosan induces water deficit stress tolerance in Gladiolus grandiflorus via regulating water relations, gaseous exchange traits, and antioxidative defense - Muhammad Rizwan; Gulzar Akhtar; Muhammad Asif Shehzad; Salman Aloufi; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; M. Nasir Khan; Özhan Şimşek; Fahad Al-Asmari; Mehmet Tütüncü; Tolga İzgü; Lala Gurbanova (Plant Biosystems, 2025)

A rapid screening method for detection of ampicillin residues in dairy milk - Nida Noreen; Bushra Akhtar; Chi-Chung Chou; Muhammad Irfan Anwar; Mian Muhammad Awais; Faqir Muhammad (Research in Veterinary Science, 2025)

Insights into genetic diversity and chlorpyrifos resistance in fall armyworm Spodoptera frugiperda (Smith) population of Pakistan - Afia Shafique; Muhammad Sarwar; Naima Razzaq; Naveed Akhtar Shad; Saba Akram; Rubab Zahra Naqvi; Muhammad Asif (Phytoparasitica, 2025)

Fabrication of bergapten loaded microneedle patch and assessment of its anti-arthritic potential against complete Freund’s adjuvant induced arthritis in Wistar rat - Qadeer Ahmad; Ammara Saleem; Zulcaif Ahmad; Muhammad Furqan Akhtar (Inflammopharmacology, 2025)

Evaluating citric and oxalic acids as sustainable chelating agents for heavy metal remediation and phytoextraction efficiency in contaminated soils using maize (Zea mays) - Ojone Anyebe; Fatihu Kabir Sadiq; Abdulalim Ahovi Sadiq; Khalid S. Almaary; Hafiz Muhammad Saleem Akhtar (Clean Technologies and Environmental Policy, 2025)

Heavy metals contamination in water, soil, and potatoes in Sargodha and Sillanwali, Pakistan, with human health implications - Kafeel Ahmad; Mutiya Zafar; Zafar Iqbal Khan; Asma Ashfaq; Muhammad Mazhar Iqbal; Tayyaba Naz; Allah Ditta; Mashal Maqsood; Shahzad Akhtar; Ijaz Rasool Noorka (Environmental Monitoring and Assessment, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Eco-friendly synthesis of N-doped carbon quantum dots from Bombax ceiba stem: A photophysical study with exploratory sensing of Fe3+/Cd2+ and dye degradation - Muhammad Arslan Akhtar; Jalwa Anum; Sameh S. Ahmed; Muhammad Ashfaq Ahmed; Asad Muhammad Khan; Christie M. Sayes; Abdur Rahim (Journal of Water Process Engineering, 2025)

Optimizing the anticancer action and toxicity evaluation of cobalt ferrite nanoparticles by different polyethylene glycol concentrations - Kanwal Akhtar; Muhammad Khawar Abbas; Nida Muzammil; Naveed Akhtar Shad; Qaisar Iqbal; Wasim Abbas; Faqir Muhammad; Bushra Akhtar; Yasir Javed; Habiba Khadim; Anam Munawar (Journal of Trace Elements in Medicine and Biology, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Tuning water transport channels in sulfonated copolymer membranes for highly effective removal of arsenic and selenium from industrial wastewater - Syed Qamber Ali Zaidi; Muhammad Hafi Wadgama; Zaib Jahan; Muhammad Bilal Khan Niazi; Faheem Hassan Akhtar (Desalination, 2025)

Legacy Polyfluoroalkyl Substances (PFAS) Contamination in Ravi and Sutlej Rivers, Punjab, Pakistan: Assessing Ecological and Human Health Risks - Naveed Akhtar; Asia Iqbal; Arshad Javid; Muhammad Tayyab (International Journal of Environmental Research, 2025)

Mechanistic insights into lead uptake and immobilization mediated by soybean biochar and arbuscular mycorrhizal fungi in Bidens parviflora - Sadam Khan; Irfan Ullah Shah Syed; Muhammad Riaz; Muhammad Tariq; Tahir shah; Sidra Sohail; Muhammad Imtiaz; Shoaib Akhtar; Jiang Yuanren; Munib Ahmad; Yurong Yang; Hanzhong Jia (Applied Soil Ecology, 2025)

Enhanced Photocatalytic Degradation of Methyl Red Dye with Bismuth-Doped ZnO: Kinetics, Mechanistic and Re-cyclability Aspects - Muhammad Alamzeb; Noor-ul-Ain Zulfiqar; Muhammad Faran Akhtar; Iqra Riaz; Faiza Ameen; Aqib Asghar; William N. Setzer (Journal of Fluorescence, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Green-synthesized amino-rich carbon quantum dots: A dual-function platform for fluorescent detection of heavy metals and degradation of malachite green dye - Jalwa Anum; Muhammad Arslan Akhtar; Asad Muhammad Khan; Khalid Ahmed; Christie M. Sayes; Ali Madi Almajwal; Jibran Iqbal; Abdur Rahim (Journal of Water Process Engineering, 2025)

Transcriptional variation of meat quality marker genes in different age and sex groups of Balkhi breed sheep - Muhammad Farooq Akhtar; Rajwali Khan; Syed Muhammad Suhail; Abdur Rehman; Ijaz Ahmad; Iftikhar Ahmad; Farhan Anwar Khan; Faraz Ahmad; Athar Rehman; Muhammad Ayaz; Khalid Khan; Amel Ayari-Akkari (Tropical Animal Health and Production, 2025)

Retraction Note: Polystichum braunii extracts inhibit Complete Freund’s adjuvant-induced arthritis via upregulation of I-κB, IL-4, and IL-10, downregulation of COX-2, PGE2, IL-1β, IL-6, NF-κB, and TNF-α, and subsiding oxidative stress - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2025)

Survey and seasonal abundances of major insect pest species in the maize fields of Punjab, Pakistan - Naveed Akhtar; Hafiz Muhammad Tahir; Azizullah; Aamir Ali; Rabia Fajar; Ayesha Muzamil; Reham Fathy; Hend O. Mohamed; Dilawar Abbas (International Journal of Tropical Insect Science, 2025)

A tetrahydropyrimidine derivative demonstrates neuroprotection against ketamine-induced schizophrenia through moderating oxidative and inflammatory markers - Tayyaba Tahir; Qurat-Ul-Ain; Ammara Saleem; Shahnaz; Muhammad Imran Khan; Kanwal Akhtar; Irfan Hamid; Rabia Iqbal; Zulcaif Ahmad; Muhammad Furqan Akhtar (Metabolic Brain Disease, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Exploring the fixed point theory and numerical modeling of fish harvesting system with Allee effect - Muhammad Waqas Yasin; Mobeen Akhtar; Nauman Ahmed; Ali Akgül; Qasem Al-Mdallal (Modeling Earth Systems and Environment, 2025)

Suppression of common scab disease in potato via application of antagonistic Trichoderma harzianum and Bacillus subtilis - Ihtisham Ul Haq; Mamoona Munir; Saira Qadir; Mushtaq Ahmad; Ayesha Ikram; Muhammad Asif; Zahid Mukhtar; Fathia Mubeen; Muhammad Akhtar; Ijaz Ahmed Qureshi (Journal of Plant Diseases and Protection, 2025)

Impact of Silicon-Based Treatments On the Demographic Traits of Spodoptera frugiperda in Maize - Muhammad Adeel Ghafar; Qin Feng; Inzamam Ul Haq; Moazam Hyder; Muhammad Sufian; Dilawar Abbas; Kamran Haider; Muhammad Lubaid Khalid; Muhammad Rahan Akhtar; Liande Wang; Rashid Iqbal; Noorah AlKubaisi; et al. (Journal of Crop Health, 2025)

Exploring the antitumor effects of Pd(II) complexes with nitrogen donor ligands towards breast carcinoma - Shazia Hussain; Sara Masood; Shabeeb Hussain; Irfan Hussain; Fouzia Malik; Muhammad Nadeem Akhtar; M. Naveed Zafar (BioMetals, 2025)

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

Phytoremediation potential of native medicinal plant species in mining degraded soil of Mohmand Northwest Pakistan - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Environmental Monitoring and Assessment, 2025)

A framework for addressing water–rock interaction (WRI) for sustainable water resources development using various simulation models: Review - Naseem Akhtar; Abdassalam A. Azamzam; Saleh Ali Tweib; Hamza Mohamed Flafel; Dani Wijaya; Leila Bouida; Pahmi Husain; Shahwaz Khan; Mohd Talha Anees; Muhammad Irman Khalif Ahmad Aminuddin; Shubham Sharma; Rajesh Singh; et al. (Environment, Development and Sustainability, 2025)

Techno-economic analysis and life cycle assessment of green hydrogen production: A case study of Sur Industrial City in Oman - Noman Raza Sial; Malik Sajawal Akhtar; Muhammad Islam; Muhammad Abdul Qyyum; Rashid Al-Abri; Ahmed Al-Hatrooshi; Ala’a H. Al Muhtaseb (Sustainable Cities and Society, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

Carbonaceous glass electrode fabricated with L-cysteine incorporated C@Fe2O3 for the ultra-selective determination of toxic metal ions - Beriham Basha; Tahani Rahil Aldhafeeri; Rabbia Tariq; Mehwish Akhtar; Norah Salem Alsaiari; M.S. Al-Buriahi; Muhammad Farooq Warsi; Sonia Zulfiqar (Journal of Water Process Engineering, 2025)

Migration and transformation behaviors of phosphorus and associated elements in wet-process phosphoric acid: Acidolysis process and mechanism study - Yuanxun Zhao; Xiaodi Li; Junxia Yu; Chenmin Li; Yaoyang Ruan; Muhammad Akhtar Abbas; Ruan Chi (Journal of Environmental Chemical Engineering, 2025)

Preparation of magnesium acetate-modified pineapple crown waste hydrochar via co-hydrothermal carbonization for a specific azo dye adsorption - Muhammad Zulfajri; Muhammad Adlim; Nurlena Andalia; Akhtar Rasool; Sri Sudewi; Genin Gary Huang (Bioresource Technology Reports, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Transdermal Co-Delivery of Sumatriptan Succinate and Naproxen Sodium via Dissolving Microneedle Patch - Azka Yousaf; Zulcaif Ahmad; Asif Mahmood; Muhammad Imran Khan; Muhammad Furqan Akhtar (Journal of Pharmaceutical Innovation, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Amelioration of Freund’s adjuvant-induced polyarthritis by Diosmin-loaded nanoparticles in Wistar rats; a mechanistic study - Hamna Mehmood; Ammara Saleem; Muhammad Furqan Akhtar; Aisha Mobashar (Inflammopharmacology, 2025)

Multifunctional Magnetic Nanoparticles for Targeted Drug Delivery Against Cancer: A Review of Mechanisms, Applications, Consequences, Limitations, and Tailoring Strategies - Shumaila Riaz; Shaukat Ali; Muhammad Summer; Urva Akhtar; Shehzeen Noor; Rimsha Haqqi; Muhammad Adeel Farooq; Iqra Sardar (Annals of Biomedical Engineering, 2025)

Extending freshness: The efficacy of ozonation in sterilizing fresh cut Malus domestica - Rutaba Zia; Arifa Tahir; Muhammad Arshad; Naseem Akhtar (Food and Humanity, 2025)

Morpho-physiological attributes, antioxidant activities, proximate seed analysis, and phytoremediative prospective of two castor bean genotypes in lead spiked soil - Sahar Naveed; Sajid Mahmood; Wajid Ishaque; Muhammad Akhtar (Acta Physiologiae Plantarum, 2025)

Biocompatible Nitro Group-Based Photosensitizer for AIE, Hypoxia, and Photodynamic Therapy. Experimental and Theoretical Approach - Maryam Rana; Munaza Pervaiz; Muhammad Arif Ali; Muhammad Ahmad; Laiqi Zhang; Shengnan Yin; Tansir Ahamad; Mansoor Akhtar (Journal of Fluorescence, 2025)

Machine learning-optimized trimetallic MOF integrated nanofibers for precise detection of p-Nitrophenol in agricultural soil - Ayesha Yousaf; Zhihua Zhao; Naeem Akhtar; Muhammad Aizaz; Maham Shahzadi (Chemical Engineering Journal, 2025)

Retraction Note: Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Spatio-temporal analysis of PM2.5 and its association with elevation by using remote sensing: the scenario of Quetta, Pakistan - Laraib Ehtasham; Malik Muhammad Akhtar; Salman Tariq; Ishaq Ahmad Mian (Air Quality, Atmosphere & Health, 2025)

HIV-1 Nef Gene Characterization and Subtype Analysis in Pakistan: A Molecular Docking Approach with Mastoparan-L Peptide - Akmal Zubair; Muhammad Ali; Naseem Akhtar (International Journal of Peptide Research and Therapeutics, 2025)

Molecular phylogeny and cryptic species identification of the genus Triplophysa in the freshwater of Malakand division, Pakistan - Omer dad; Muhammad Fiaz Khan; Akhtar Rasool; Mohammad Attaullah; Muhammad Israr; Naveed Akhtar (Zoologischer Anzeiger, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Modeling of ground motion data to assess the seismic features for monitoring the seismic activity - Samiya Akhtar; Muhammad Mohsin; Zulfiqar Ali (Natural Hazards, 2025)

Implications of nociceptor receptors and immune modulation: emerging therapeutic targets for autoimmune diseases - Syeda Asloob Fatima; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Muhammad Shahid; Fozia Anjum; Fatma Hussain; Aisha Mobashar; Maham Ashraf (Inflammopharmacology, 2025)

Graphene-Based Multi-Nanocomposites: Synthesis, Characterization and Photodegradation Analysis - Adeeba Sadia; Muhammad Irshad; Muhammad Faran Akhtar; Shaukat Ali; Muhammad Summer (Journal of Fluorescence, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

A comprehensive review on guava: Nutritional profile, bioactive potential, and health-promoting properties of its pulp, peel, seeds, pomace and leaves - Farwa Iqbal Khan; Saeed Akhtar; Muhammad Qamar; Tariq Ismail; Wisha Saeed; Tuba Esatbeyoglu; Seid Mahdi Jafari (Trends in Food Science & Technology, 2025)

Equus remains from the Pleistocene deposits of Sardhok Pabbi Hills, Pakistan - Muhammad Akbar Khan; Kiran Aftab; Sayyed Ghyour Abbas; Muhammad Khaled Siddiq; Khalid Mahmood; Muhammad Adeeb Babar; Muhammad Akhtar (Geobios, 2025)

Development and evaluation of methotrexate-loaded nanoemulsion formulation for topical treatment of psoriasis - Sheikh Abdur Rashid; Faiza Naseem; Pervaiz Akhtar Shah; Hamna Batool Hashmi; Mudassar Mazher; Mohammad S. Mubarak; Javad Sharifi-Rad; Muhammad Badar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Geochemical evolution, geostatistical mapping and machine learning predictive modeling of groundwater fluoride: a case study of western Balochistan, Quetta - Taimoor Shah Durrani; Malik Muhammad Akhtar; Kaleem U. Kakar; Muhammad Najam Khan; Faiz Muhammad; Maqbool khan; H. Habibullah; Changaiz Khan (Environmental Geochemistry and Health, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Mitigation of salinity stress in sunflower plants (Helianthus annuus L.) through topical application of salicylic acid and silver nanoparticles - Muhammad Shahbaz; Tauseef Anwar; Sammer Fatima; Nilgün Onursal; Huma Qureshi; Waseem Akhtar Qureshi; Naimat Ullah; Walid Soufan; Wajid Zaman (Physiology and Molecular Biology of Plants, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

RETRACTED ARTICLE: Esculin-loaded nanoparticles ameliorate adjuvant-induced polyarthritis via subduing inflammatory and oxidative stress biomarkers in Wistar rats - Mehak Fatima; Ammara Saleem; Muhammad Furqan Akhtar; Kanwal Akhtar; Muhammad Imran Khan (Inflammopharmacology, 2025)

Carvone-loaded chitosan nanoparticles alleviate joint destruction by downregulating the expression of pro, inflammatory cytokines and MMP-13 in adjuvant-induced rat model - Zartashia Kanwal; Bushra Akhtar; Bilal Aslam; Muhammad Imran Arshad (Inflammopharmacology, 2025)

Formation of particulate matter in the ambient air of Dhaka city, Bangladesh - Md. Yeasin Pabel; Md. Fakrul Islam; Muhammad Nurul Huda; Shahid Akhtar Hossain; M. Muhibur Rahman; Md. Mominul Islam (Air Quality, Atmosphere & Health, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Synergistic effects of N-containing heterocyclic and Ca ligand structures on the phosphorus adsorption of N/Ca co-doped biochar - Zhengming Yang; Zhidong Zou; Muhammad Asif Akhtar; Wenjuan Niu; Luna Ren; Shu Zhang; Nian Liu; Hongliang Cao (Journal of Cleaner Production, 2024)

Machine learning integration with response surface methodology to enhance the removal efficacy of arsenate (V) through sulfur-functionalized mxene coated QPPO/PVA AEM - Nimra Saher Zain; Ibrahim A. Shaaban; Farhan Zafar; Hafiz Muhammad Asif; Muhammad Tariq; Muhammad Ali Khan; Naeem Akhtar; Hafsa Kainat; Mohammad A. Assiri (Journal of Environmental Management, 2024)

Machine learning trained poly (3,4-ethylenedioxythiophene) functionalized carbon matrix suspended Cu nanoparticles for precise monitoring of nitrite from pickled vegetables - Waseem Abbas; Farhan Zafar; Manal F. Abou Taleb; Mavra Ameen; Abdul Sami; Muhammad Ehsan Mazhar; Naeem Akhtar; Muhammad Waseem Fazal; Mohamed M. Ibrahim; Zeinhom M. El-Bahy (Food Chemistry, 2024)

Removal of airborne particulate matter by evergreen tree species in Dhaka, Bangladesh - Saif Shahrukh; Richard Baldauf; Robert Popek; Mohammad Moniruzzaman; Muhammad Nurul Huda; Md. Mominul Islam; Shahid Akhtar Hossain; Mohammad Enayet Hossain (Environmental Pollution, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Deposition and diagenesis of the Triassic-Jurassic limestone successions of the northwestern passive margin of the Indian plate, Sulaiman Fold-Thrust Belt, Pakistan - Razzaq Abdul Manan; Akhtar Muhammad Kassi; Henrik Friis; Aimal Khan Kasi; Syed Haroon Ali; Mohammad Ahmed Farooqui; Muhammad Ishaq Kakar (Carbonates and Evaporites, 2024)

Elucidating the protective role of manganese seed priming in mitigating lead-induced oxidative stress: enhancements in growth, grain yield, and antioxidant activities of wheat - Abida Parveen; Muhammad Atif; Faiza Akhtar; Shagufta Perveen; Sara Zafar; Khadija Hafeez; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Efficacy of Melia azedarach leaf extract in different solvents against Heterotermes indicola Wasmann (Blattodea: Rhinotermitidae) using non-durable wooden blocks under laboratory and field conditions - Muhammad Afzal; Hamid-ur Rehman; Ismail Zeb; Naveeda Akhtar Qureshi (South African Journal of Botany, 2024)

Profusion of microplastics in dental healthcare units; morphological, polymer, and seasonal trends with hazardous consequences for humans - Naseem Akhtar; Arifa Tahir; Abdul Qadir; Rehana Masood; Zain Gulzar; Muhammad Arshad (Journal of Hazardous Materials, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Oleuropein: Chemistry, extraction techniques and nutraceutical perspectives-An update - Anees Ahmed Khalil; Md. Mominur Rahman; Abdur Rauf; Md. Rezaul Islam; Sultana Juhara Manna; Ammar Ahmed Khan; Samee Ullah; Muhammad Nadeem Akhtar; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

From port to planet: Assessing NO2 pollution and climate change effects with Sentinel-5p satellite imagery in maritime zones - Mohd Azhafiz Abdullah; L.F. Chuah; Samsuri Bin Abdullah; Awais Bokhari; Asad Syed; Abdallah M. Elgorban; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman; Saira Asif (Environmental Research, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Integrated study for assessing groundwater dynamics of the Dehdan village, Haripur Basin, Pakistan - Umair Bin Nisar; Siddique Akhtar Ehsan; Muhammad Imran Rafiq; Muhammad Rizwan Mughal (Journal of Applied Geophysics, 2024)

Antioxidative enzymes, phytochemicals and proximate components in jujube fruit (Ziziphus mauritiana L.) with respect to genotypes and harvest maturity - Zohaib Asghar; Muhammad Amin; Sami Ullah; Hamad Hassan; Umm-e Habiba; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Aiyub; Shafa Nayab; Ambreen Naz; et al. (Food Bioscience, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Retraction Note: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2024)

Unlocking plant secrets: A systematic review of 3D imaging in plant phenotyping techniques - Muhammad Salman Akhtar; Zuhair Zafar; Raheel Nawaz; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2024)

Evaluating climate change impacts on reef environments via multibeam echosounder and Acoustic Doppler Current profiler technology - Mohd Azhafiz Abdullah; L.F. Chuah; Razak Zakariya; Asad Syed; Rozaimi Che Hasan; Shahrul Miza Mahmud; Abdallah M. Elgorban; A. Bokhari; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman (Environmental Research, 2024)

Reduction of bitter taste receptor gene family in folivorous colobine primates relative to omnivorous cercopithecine primates - Min Hou; Muhammad Shoaib Akhtar; Masahiro Hayashi; Ryuichi Ashino; Akiko Matsumoto-Oda; Takashi Hayakawa; Takafumi Ishida; Amanda D. Melin; Hiroo Imai; Shoji Kawamura (Primates, 2024)
Bitter taste perception is important in preventing animals from ingesting potentially toxic compounds. Whole-genome assembly (WGA) data have revealed that bitter taste receptor genes ( TAS2R s) comprise a multigene family with dozens of intact and disrupted genes in primates. However, publicly available WGA data are often incomplete, especially for multigene families. In this study, we employed a targeted capture (TC) approach specifically probing TAS2R s for ten species of cercopithecid primates with diverse diets, including eight omnivorous cercopithecine species and two folivorous colobine species. We designed RNA probes for all TAS2R s that we modeled to be intact in the common ancestor of cercopithecids (“ancestral-cercopithecid TAS2R gene set”). The TC was followed by short-read and high-depth massive-parallel sequencing. TC retrieved more intact TAS2R genes than found in WGA databases. We confirmed a large number of gene “births” at the common ancestor of cercopithecids and found that the colobine common ancestor and the cercopithecine common ancestor had contrasting trajectories: four gene “deaths” and three gene births, respectively. The number of intact TAS2R genes was markedly reduced in colobines (25–28 detected via TC and 20–26 detected via WGA analysis) as compared with cercopithecines (27–36 via TC and 19–30 via WGA). Birth or death events occurred at almost every phylogenetic-tree branch, making the composition of intact genes variable among species. These results show that evolutionary change in intact TAS2R genes is a complex process, refute a simple general prediction that herbivory favors more TAS2R genes, and have implications for understanding dietary adaptations and the evolution of detoxification abilities.

Lophochoerus nagrii (Suidae) from the Siwaliks (Neogene) of Pakistan - Muhammad Adeeb Babar; Sayyed Ghyour Abbas; Muhammad Akbar Khan; Muhammad Akhtar (Annales de Paléontologie, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

Unraveling the contribution of copper seed priming in enhancing chromium tolerance in wheat by improving germination, growth, and grain yield - Khadija Hafeez; Muhammad Atif; Shagufta Perveen; Abida Parveen; Faiza Akhtar; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Detailed sedimentological investigation of the late cretaceous fort munro formation, western sulaiman range, Pakistan - Badar U Zaman; Mohibullah Mohibullah; Razzaq Abdul Manan; Akhtar Muhammad Kassi; Muhammad Rizwan (Carbonates and Evaporites, 2024)

Tourism triumphs: unraveling the essence of Asia’s allure through governance, FDI, and natural bounties - Muhammad Zaheer Akhtar; Khalid Zaman; Muhammad Azhar Khan (Journal of Environmental Studies and Sciences, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

Diltiazem HCl suppresses porcine reproductive and respiratory syndrome virus infection in susceptible cells and in swine - Liangliang Li; Jiayu Wang; Li Chen; Qinghai Ren; Muhammad Faheem Akhtar; Wenhua Liu; Changfa Wang; Shengliang Cao; Wenqiang Liu; Qin Zhao; Yubao Li; Tongtong Wang (Veterinary Microbiology, 2024)

Artificial intelligence-based prediction models of bio-treated sand strength for sustainable and green infrastructure applications - Muhammad Naqeeb Nawaz; Ahmed Yar Akhtar; Waqas Hassan; Muhammad Hasnain Ayub Khan; Muhammad Muneeb Nawaz (Transportation Geotechnics, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Biomonitoring potentially toxic elements in atmospheric particulate matter of greater Dhaka region using leaves of higher plants - Zuairia Binte Jashim; Saif Shahrukh; Shahid Akhtar Hossain; Jahan-E-Gulshan; Muhammad Nurul Huda; Md. Mominul Islam; Mohammad Enayet Hossain (Environmental Monitoring and Assessment, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

Electricity shortfalls and financial leverage of listed firms in Pakistan - Muhammad Akhtar; Muhammad Haris; Hafiz Muhammad Naveed; Yasir Rasool; Mamdouh Abdulaziz Saleh Al-Faryan (Utilities Policy, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Water resource management and flood mitigation: hybrid decomposition EMD-ANN model study under climate change - Nisar Ahmad; Xu Yi; Muhammad Tayyab; Muhammad Hamza Zafar; Naureen Akhtar (Sustainable Water Resources Management, 2024)
The growing population and the rise in urbanization have made managing water a critical concern around the world in recent years. Globally, flooding is one of the most devastating natural disasters. Flood risk mitigation relies heavily on accurate and consistent streamflow forecasts. Pakistan Upper Indus Basin (UIB) is most vulnerable to flooding. Floods have become more frequent in recent decades. UIB can be divided into sub-regions due to its landscape variability, and its collective impact is most prominent in the Massam region. UIB hydrological and meteorological station observations have been used to study seasonal hydro-meteorological variations. To predict flooding, this study proposes a hybrid model combining artificial neural networks as multi-layer perceptron (MLPs) in feed-forward mode, along with empirical mode decomposition (EMD). Data collected by the surface-water hydrology project and Pakistan Meteorological Department from 1960 to 2012, 1969 to 2012, and 1972 to 2012 have been utilized from 17 locations. Statistical parameters and Nash–Sutcliffe Efficiency were measured to analyze the model’s prowess. As a result, decomposition-based models perform better than AI-based models when it comes to prediction accuracy. MLPQTP-EMD performed exceptionally better than competing AI models. The results are further validated by performing a peak value analysis during the flooding season (June–September) achieving a remarkable 91.3% score adding a 5.6% increase by EMD for input data achieving 39.3–32.3% statistical indices scores.

Retraction Note: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md.Mominur Rahman; Md.Rezaul Islam; Sheikh Shohag; Md.Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md.Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md.Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

UV-spectrophotometric Optimization of Temperature, pH, Concentration and Time for Eucalyptus Globulus Capped Silver Nanoparticles Synthesis, their Characterization and Evaluation of Biological Applications - Ansar Aziz Subhani; Muhammad Irshad; Shaukat Ali; Muhammad Jawad; Muhammad Faran Akhtar; Muhammad Summer (Journal of Fluorescence, 2024)

Retraction Note: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

Wound healing, antioxidant and antibacterial activities of polyphenols of Psidium guajava L. leaves - Kainat Bilal; Fatima Mehboob; Nosheen Akhtar; Irfan Ali Mirza; Muhammad K. Okla; M. Junaid Dar; Ibrahim A. Saleh; Naser Zomot; Humaira Fatima (South African Journal of Botany, 2024)

Digital transformation, supplier concentration, and CEO financial experience: Unveiling the dynamics of innovation performance in Chinese firms - Hua Zhang; Xiaohui Wang; Muhammad Waheed Akhtar (Journal of Cleaner Production, 2024)

Novel active composite films based on carboxymethyl cellulose and sodium alginate incorporated with phycocyanin: Physico-chemical, microstructural and antioxidant properties - Hafiz Muhammad Saleem Akhtar; Ya Zhao; Li Li; Qilong Shi (Food Hydrocolloids, 2024)

Sustainable humidity control in the built environment: Recent research and technological advancements in thermal driven dehumidification systems - Muhammad Usman Saeed Akhtar; Sulaiman O. Fadlallah; Muhammad Imran Khan; Faisal Asfand; Sami G. Al-Ghamdi; Rakesh Mishra (Energy and Buildings, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Decarbonising ASEAN coastal shipping: Addressing climate change and coastal ecosystem issues through sustainable carbon neutrality strategies - Olakunle Oloruntobi; Lai Fatt Chuah; Kasypi Mokhtar; Adel Gohari; Ahmed Rady; Rasha E. Abo-Eleneen; Muhammad Saeed Akhtar; Muhammad Mubashir (Environmental Research, 2024)

A wearable self-powered microneedle system based on conductive drugs for infected wound healing: A new electrical stimulation delivery strategy - Shanguo Zhang; Tianyi Jiang; Fang Han; Liangyu Cao; Ming Li; Zhenyou Ge; Haoxiu Sun; Hao Wu; Wenlong Wu; Nannan Zhou; Muhammad Luqman Akhtar; Hongyuan Jiang (Chemical Engineering Journal, 2024)

Effects of seismic risk analysis on regional sectors using both the deterministic and stochastic modeling - Muhammad Imran Hanif; Rehman Akhtar (Natural Hazards, 2024)

Zinc Oxide Nanoparticles Significant Role in Poultry and Novel Toxicological Mechanisms - Arjmand Fatima; Tean Zaheer; Kaushik Pal; Rao Zahid Abbas; Tayyaba Akhtar; Sultan Ali; Muhammad Shahid Mahmood (Biological Trace Element Research, 2024)

Unlocking green innovation and environmental performance: the mediated moderation of green absorptive capacity and green innovation climate - Sadaf Akhtar; Cai Li; Jan Muhammad Sohu; Yasir Rasool; Muhammad Iatzaz Ul Hassan; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

Assessing coastal bathymetry and climate change impacts on coastal ecosystems using Landsat 8 and Sentinel-2 satellite imagery - Kasypi Mokhtar; Lai Fatt Chuah; Mohd Azhafiz Abdullah; Olakunle Oloruntobi; Siti Marsila Mhd Ruslan; Gadah Albasher; Atif Ali; Muhammad Saeed Akhtar (Environmental Research, 2023)

Influence of Oxyranylmethanol as a Catalytic Cross-linking Agent over Physiochemical Properties and Pb (II) Adsorption Performance of Resorcinol Formaldehyde Aerogels: a Comparative Study - Faheem Akhter; Abdul Rauf Jamali; Jawad Ahmed; Haris Jawad Arain; Muhammad Junaid Ahsan; Muhammad Naeem Akhtar (Water, Air, & Soil Pollution, 2023)

Expression deregulation of genes related to DNA repair and lead toxicity in occupationally exposed industrial workers - Zertashia Akram; Ishrat Mahjabeen; Mariam Batool; Sana Kanwal; Fatima Nawaz; Mahmood Akhtar Kayani; Muhammad Rizwan (International Archives of Occupational and Environmental Health, 2023)

Appraisal of anti-arthritic potential of Coronopus didymus (L.) Sm. aqueous extract and its safety study in Wistar rats - Ammara Saleem; Huma Khalid; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2023)

Curative potential of Populus ciliata Wall ex. Royle extract against adjuvant-induced arthritis and peripheral neuropathy in Wistar rats - Amna Tahir; Muhammad Furqan Akhtar; Ammara Saleem; Muhammad Naveed; Basiru Olaitan Ajiboye; Fareeha Anwar; Aslam Khan (Inflammopharmacology, 2023)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Development of ZnO-GO-NiO membrane for removal of lead and cadmium heavy metal ions from wastewater - Arslan Maqbool; Ameen Shahid; Zaib Jahan; Muhammad Bilal Khan Niazi; Muhammad Ali Inam; Ahmed M. Tawfeek; Emadeldin M Kamel; Muhammad Saeed Akhtar (Chemosphere, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Paper based colorimetric sensor using novel green magnetized nanocomposite of pinus for hydrogen peroxide detection in water and milk - Mehrosh Buzdar; Asim Yaqub; Akhtar Hayat; Muhammad Zia Ul Haq; Aizaz Khan; Huma Ajab (Food Bioscience, 2023)

Impact of graded levels of coated calcium butyrate on growth performance and serological indices during pre-weaning stage in Holstein calves - Abdur Rahman; Muhammad Furhan Arshad; Shah Nawaz; Zafar Hayat; Syed Ehtisham ul Haque; Saima Saima; Akhtar Rasool Asif; Muawuz Ijaz; Muhammad Zeeshan Anwar (Tropical Animal Health and Production, 2023)

Redundant nerve roots indicate higher degree of stenosis in lumbar spine stenotic patients - Karim Rizwan Nathani; Muhammad Danish Barakzai; Hamid Hussain Rai; Komal Naeem; Fatima Mubarak; Haissan Iftikhar; Saad Akhtar Khan; Syed Ather Enam (Acta Neurologica Belgica, 2023)

Retraction Note: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2023)

The impact of financial innovation, green energy, and economic growth on transport-based CO2 emissions in India: insights from QARDL approach - Snovia Naseem; Umair Kashif; Yasir Rasool; Muhammad Akhtar (Environment, Development and Sustainability, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

Wood as a green and sustainable alternative for environmentally friendly & flexible electronic devices - Hizbullah Malik; Muhammad Bilal Khan Niazi; Waheed Miran; Ahmed M. Tawfeek; Zaib Jahan; Emadeldin M. Kamel; Nouman Ahmed; Muhammad Saeed Akhtar (Chemosphere, 2023)

In-vivo anticoccidial efficacy of green synthesized iron-oxide nanoparticles using Ficus racemosa Linn leaf extract. (Moraceae) against Emeria tenella infection in broiler chicks - Asiya Khan; Muhammad Afzal; Khadija Rasool; Muhammad Ameen; Naveeda Akhtar Qureshi (Veterinary Parasitology, 2023)

Effects of different fat replacers on functional and rheological properties of low-fat mozzarella cheeses: A review - Aqsa Akhtar; Iqra Nasim; Muhammad Saeed ud Din; Tetsuya Araki; Nauman Khalid (Trends in Food Science & Technology, 2023)

Synthesis, chracterization, and analytical application of silver dopamine magnetic nanomaterial - Rahat Nawaz; Zarayb Hussan; Fahad Ali; Naeem Akhtar; Batool Fatima; Muhammad Najam ul Haq; Awais Bokhari; Salman Raza Naqvi; Mohamed Ouladsmane; Saadat Majeed (Fuel, 2023)

Heterologous expression of bacterial dehydrin gene in Arabidopsis thaliana promotes abiotic stress tolerance - Nadir Zaman Khan; Akhtar Ali; Waqar Ali; Muhammad Aasim; Tariq Khan; Zaryab Khan; Iqbal Munir (Physiology and Molecular Biology of Plants, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Role of Exogenous Osmolyte Supplementation in Ameliorating Osmotic and Oxidative Stress and Promoting Growth in Salinity-Stressed Soybean Genotypes - Muhammad Anwar-ul-Haq; Irfan Iftikhar; Javaid Akhtar; Muhammad Maqsood (Journal of Soil Science and Plant Nutrition, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

"The promissory note at COP-21 of sustainable energy for all" Is it converging toward economic development? - Muhammad Javeed Akhtar; Hafeez Ur Rehman; Qaisar Abbas (Environment, Development and Sustainability, 2023)

An insight into the hepatoprotective role of Velpatasvir and Sofosbuvir per se and in combination against carbon tetrachloride-induced hepatic fibrosis in rats - Sadaf Yasmeen; Aslam Khan; Fareeha Anwar; Muhammad Furqan Akhtar; Sidra Yasmeen; Shafeeq Ali Shah (Environmental Science and Pollution Research, 2023)

Diosgenin, a steroidal sapogenin, arrests arthritis through modulation of inflammatory cytokines and oxidative stress biomarkers in Wistar rats - Maira Javed; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2023)

Chrysin, a 5,7-dihydroxyflavone restrains inflammatory arthritis in rats via subsiding oxidative stress biomarkers and inflammatory cytokines - Afnan Afnan; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2023)

Clinicopathological profile of peritoneal tuberculosis and a new scoring model for predicting mortality: an international ID-IRI study - Alpaslan Tanoglu; Hakan Erdem; Jon S. Friedland; Handan Ankaralı; Jose Fernando Garcia-Goez; Ayse Albayrak; Amani El-Kholy; Sevil Alkan Ceviker; Fatma Amer; Serpil Erol; Ilad Alavi Darazam; Mohammad Mahdi Rabiei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Exploring the nexus between green innovations and green growth in G-7 economies: evidence from wavelet quantile correlation and continuous wavelet transform causality methods - Umer Zaman; Muhammad Zubair Chishti; Touseef Hameed; Muhammad Sohail Akhtar (Environmental Science and Pollution Research, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Heavy Metal Occurrence, Pathways, and Associated Socio-ecological Risks in Riverine Water: Application of Geographic Information System, Multivariate Statistics, and Risk Assessment Models - Kifayatullah Khan; Muhammad Younas; Muhammad Sajawal Khan; Xu Li; Muhammad Fawad; Noor Samad Shah; Jafar Ali; Sana Ullah; Muhammad Ayaz; Afsheen Maryam; Asmat Ali; Akhtar Zeb Khan; et al. (Water, Air, & Soil Pollution, 2023)

U–Pb zircon geochronology and geochemistry of Luk Ulo River boulders belong to Late Cretaceous-Paleocene metapsammite and metagranite of Luk Ulo Karangsambung, Central Java, Indonesia - Muhammad Irman Khalif Ahmad Aminuddin; Mohd Shuaib; Naseem Akhtar; Nugroho Imam Setiawan; I. Wayan Warmada (Environmental Science and Pollution Research, 2023)

Do military expenditures impede economic growth in 48 Islamic countries? A panel data analysis with novel approaches - Liu Geng; Olivier Joseph Abban; Yao Hongxing; Charles Ofori; Joana Cobbinah; Sarah Akosua Ampong; Muhammad Akhtar (Environment, Development and Sustainability, 2023)

Phytochemical analysis, in-vitro biological activities and Pearson correlation of total polyphenolic content with antioxidant activities of Ziziphus mauritiana fruit pulp and seed during different ripening stages - Shehla Parveen; Naeema Bukhari; Mamona Nazir; Waseem Akhtar Qureshi; Asma Yaqoob; Muhammad Shahid (South African Journal of Botany, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Adverse health effects and mechanisms of microplastics on female reproductive system: a descriptive review - Vishal Afreen; Kanza Hashmi; Rimsha Nasir; Ammara Saleem; Muhammad Imran Khan; Muhammad Furqan Akhtar (Environmental Science and Pollution Research, 2023)

Biocompatible cellulose acetate supported ammonium based ionic liquid membranes; way forward to remediate water pollution - Amina Khalid; Sana Zulfiqar; Noshabah Tabassum; Amir Sada Khan; Muhammad Amin Abid; Muhammad Saeed Akhtar; Fahad Al-Misned; Ahmed Muteb Aljuwayid; Sasan Zahmatkesh; Saira Asif (Chemosphere, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

Glutathione treatment suppresses the adverse effects of microplastics in rice - Fu Chen; Muhammad Aqeel; Noreen Khalid; Muhammad Kashif Irshad; Fozia Farhat; Atia Nazir; Jing Ma; Muhammad Saeed Akhtar; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Ali Noman (Chemosphere, 2023)

Membrane reactor for production of biodiesel from nonedible seed oil of Trachyspermum ammi using heterogenous green nanocatalyst of manganese oxide - Rozina; Mushtaq Ahmad; Muhammad Zafar; Awais Bokhari; Muhammad Saeed Akhtar; Razan A. Alshgari; Abdulnasser Mahmoud Karami; Saira Asif (Chemosphere, 2023)

Synthesis, characterization and adsorption behavior of modified cellulose nanocrystals towards different cationic dyes - Tariq Aziz; Arshad Farid; Sampath Chinnam; Fazal Haq; Mehwish Kiran; Ab Waheed Wani; Zeid A. Alothman; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Muhammad Saeed Akhtar (Chemosphere, 2023)

Membrane-processed honey samples for pollen characterization with health benefits - Nabila; Mushtaq Ahmad; Ashwaq T. Althobaiti; Wahid Ali; Khansa Masood; Mohamed Fawzy Ramadan; Bisha Chaudhary; Muhammad Zafar; Muhammad Saeed Akhtar; Shazia Sultana; Sasan Zahmatkesh; Tariq Mehmood; et al. (Chemosphere, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

Spatial Distribution of Eucalyptus Plantation and its Impact on the Depletion of Groundwater Resources of Tehsil Swat Ranizai, District Malakand - Muhammad Jamal Nasir; Waqar Akhtar; Vipin Kumar Oad (Arabian Journal of Geosciences, 2023)

Reproductive and metabolic toxic effects of polystyrene microplastics in adult female Wistar rats: a mechanistic study - Anam Saeed; Muhammad Furqan Akhtar; Ammara Saleem; Bushra Akhtar; Ali Sharif (Environmental Science and Pollution Research, 2023)

Energy consumption, CO2 emissions, foreign direct investment, and economic growth in Malaysia: an NARDL technique - Rulia Akhtar; Muhammad Mehedi Masud; Abdullah Al-Mamun; Abu Naser Mohammad Saif (Environmental Science and Pollution Research, 2023)

COVID-19, travel restrictions and environmental consequences - Muhammad Usman; Li Yuyan; Mudassir Husnain; Muhammad Waheed Akhtar (Environment, Development and Sustainability, 2023)

Tissue specific expression of bacterial cellulose synthase (Bcs) genes improves cotton fiber length and strength - Sidra Akhtar; Ahmad Ali Shahid; Sana Shakoor; Mukhtar Ahmed; Sehrish Iftikhar; Muhammad Usmaan; Sahar Sadaqat; Ayesha Latif; Adnan Iqbal; Abdul Qayyum Rao (Plant Science, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Spatial variation in groundwater quality with respect to surface water seepages in Kadhan area District Badin (Indus Delta), Sindh, Pakistan - Muhammad Afzal Jamali; Akhtar Hussain Markhand; Muhammad Hassan Agheem; Shafquat Hussain Zardari; Asfand Yar Wali Arain (International Journal of Energy and Water Resources, 2023)

Characteristics and epidemiological investigation of equid herpesvirus 8 in donkeys in Shandong, China - Tongtong Wang; Cankun Xi; Yue Yu; Wenqiang Liu; Muhammad Faheem Akhtar; Yubao Li; Changfa Wang; Liangliang Li (Archives of Virology, 2023)

“Ficus johannis Boiss. leaves ethanolic extract ameliorate streptozotocin-induced diabetes in rats by upregulating the expressions of GCK, GLUT4, and IGF and downregulating G6P” - Afshan Asghar; Ali Sharif; Sana Javaid Awan; Bushra Akhtar; Muhammad Furqan Akhtar; Sajid Ali; Shahnaz (Environmental Science and Pollution Research, 2023)

Transformation of waste seed biomass of Cordia myxa into valuable bioenergy through membrane bioreactor using green nanoparticles of indium oxide - Rozina; Mabkhoot Alsaiari; Mushtaq Ahmad; Muhammad Zafar; Farid A. Harraz; Jari S. Algethami; Biljana Šljukić; Diogo M.F. Santos; Muhammad Saeed Akhtar (Chemosphere, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

A computationally efficient unscented Kalman smoother for ameliorated tracking of subatomic particles in high energy physics experiments - Jahanzeb Akhtar; Imran Ghous; Muhammad Jawad; Zhaoxia Duan; Ikram Ullah Khosa; Saim Ahmed (Computer Physics Communications, 2023)

Centella asiatica (L.) Urb. Extract ameliorates branched-chain amino acid (BCAA) metabolism in acute reserpine-induced stress zebrafish model via 1H Nuclear Magnetic Resonance (NMR)-based metabolomics approach - Fauziahanim Zakaria; Muhammad Tayyab Akhtar; Wan Ibrahim Wan Norhamidah; Abu Bakar Noraini; Azira Muhamad; Shamarina Shohaimi; Maulidiani; Hafandi Ahmad; Intan Safinar Ismail; Nor Hadiani Ismail; Khozirah Shaari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Quercetin-loaded chitosan nanoparticles ameliorate adjuvant-induced arthritis in rats by regulating anti-oxidant enzymes and downregulating pro- and inflammatory cytokines - Abdul Hannan; Bushra Akhtar; Ali Sharif; Fozia Anjum; Imran Pasha; Ahrar Khan; Muhammad Furqan Akhtar; Ammara Saleem (Inflammopharmacology, 2023)

The investigation of heavy metal concentration through GIS-based approach from groundwater of Umerkot city, Sindh, Pakistan - Muhammad Afzal Jamali; Akhtar Hussain Markhand; Dileep Kumar; Asfand Yar Wali Arain; Mahdi Hassan Mahar (Arabian Journal of Geosciences, 2023)

Assessment of aflatoxin M 1 exposure and associated determinants in children from Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Fareeha Akhtar; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2023)

Effects of furanic compounds from biomass pyrolysis on ketonization reaction: The role of oxygenated side groups - Wenran Gao; Yiling Wan; Shanhui Zhao; Muhammad Asif Akhtar; Kuan Ding; Bin Li; Yinlong Wu; Shoujun Zhang; Shu Zhang (Fuel, 2023)

Phytoremediation of Metal-Contaminated Soils and Water in Pakistan: a Review - Muhammad Shahbaz Akhtar; Ahmad Hameed; Sohaib Aslam; Razi Ullah; Aima Kashif (Water, Air, & Soil Pollution, 2023)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

Observed trends and variability of seasonal and annual precipitation in Pakistan during 1960–2016 - Azfar Hussain; Jianhua Cao; Shaukat Ali; Sher Muhammad; Waheed Ullah; Ishtiaq Hussain; Mobeen Akhtar; Xiuqin Wu; Yinghui Guan; Jinxing Zhou (International Journal of Climatology, 2022)
Long‐term precipitation monitoring plays a vital role in water resource management and disaster prevention and mitigation. This study assesses spatial and temporal trends in seasonal and annual precipitation in Pakistan between 1960 and 2016 at an interannual scale. The Mann–Kendall (MK) test, Sen's slope (SS) estimator, and Sequential Mann–Kendall (SQMK) test were employed to assess trends. Cluster analysis and L ‐moment approach were used to identify the homogenous precipitation regions. In general, increasing precipitation trends between 1960 and 2016 were evident. Results indicated increasing precipitation in winter, autumn, summer and annual scale at the rates of 0.20, 2.18, 5.16, and 10.89 mm·decade −1 , respectively. In spring, the precipitation trend shows a decreasing trend at −0.67 mm·decade −1 . Moreover, a significant decreasing trend occurred in winter in southern Pakistan. The overall increasing trends were more noticeable between 1960 and 1988, compared to the declining precipitation during 1989–2016. SQMK analysis indicates a clear downward trend in most regions during 1989–2016, except in autumn. Annual precipitation has increased topographically except at 500 m and 1,500 m during 1960–2016 with a significant increase of 1.37 mm·decade −1 at elevation

Treatment of Acidic Wastewater Effluents and Defluoridation by Lime Materials - Muhammad Shahbaz Akhtar (Water Conservation Science and Engineering, 2022)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

DNA binding and cleavage, BRCA1 gene interaction, antiglycation and anticancer studies of transition metal complexes of sulfonamides - Arusa Akhtar; Muhammad Danish; Awais Asif; Muhammad Nadeem Arshad; Abdullah M. Asiri (Molecular Diversity, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

EMS-based mutants are useful for enhancing drought tolerance in spring wheat - Sadaf Zahra; Momina Hussain; Sana Zulfiqar; Shumila Ishfaq; Tayyaba Shaheen; Muhammad Akhtar; Mehboob-ur-Rahman (Cereal Research Communications, 2022)

Mechanistic insights on the possible protective role of polyphenols extracted from Tamarix aphylla aerial parts against sodium arsenite-induced hepatotoxicity in rats - Shaher Bano; Ali Sharif; Bushra Akhtar; Mohamed M. Abdel-Daim; Muhammad Furqan Akhtar; Faiza Liaqat Ali (Environmental Science and Pollution Research, 2022)

Correction to: Effect of eco‑friendly probiotics‑supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Dysregulated expression of microRNAs acts as prognostic and diagnostic biomarkers for glioma patients - Yusrah Masood; Manahil Shal; Muhammad Furqan Shah; Maria Fazal Ul Haq; Mahmmood Akhtar Kayani; Ishrat Mahjabeen (Molecular Genetics and Genomics, 2022)

Effect of eco-friendly probiotics-supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2022)

Re-examining the nexuses of communicable diseases, environmental performance, and dynamics of sustainable Development in OECD countries - Zhang Yu; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Muhammad Sajid Amin; Laeeq Razzak; Muhammad Tariq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Fabrication of polysulfone mixed matrix membrane for wastewater treatment - Kousar Parveen; Uzaira Rafique; Muhammad Javed Akhtar (Journal of Environmental Health Science and Engineering, 2022)

Resveratrol and neuroprotection: an insight into prospective therapeutic approaches against Alzheimer’s disease from bench to bedside - Fahadul Islam; Mohamed H. Nafady; Md. Rezaul Islam; Susmita Saha; Salma Rashid; Aklima Akter; Md. Harun- Or-Rashid; Muhammad Furqan Akhtar; Asma Perveen; Ghulam Md. Ashraf; Md. Habibur Rahman; Sherouk Hussein Sweilam (Molecular Neurobiology, 2022)

Correction to: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Therapeutic potential of dopamine agonists in the treatment of type 2 diabetes mellitus - Md. Tanvir Kabir; Jannatul Ferdous Mitu; Raushanara Akter; Muhammad Furqan Akhtar; Ammara Saleem; Ahmed Al-Harrasi; Saurabh Bhatia; Md. Sohanur Rahman; Fouad Damiri; Mohammed Berrada; Md. Habibur Rahman (Environmental Science and Pollution Research, 2022)

Mix-method modelling of actors’ capacity for environmental sustainability and climate compatible development in energy sector - Kanwar Muhammad Javed Iqbal; Nadia Akhtar; Muhammad Owais Khan; Muhammad Irfan Khan (Environmental Science and Pollution Research, 2022)

Efficient photocatalytic degradation of nitrobenzene by copper-doped TiO2: kinetic study, degradation pathway, and mechanism - Tehmina Akhtar; Habib Nasir; Effat Sitara; Syeda Aqsa Batool Bukhari; Sharif Ullah; Rana Muhammad Arslan Iqbal (Environmental Science and Pollution Research, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Impact of various oviposition substrates on biology of pink bollworm Pectinophora gossypiella (Lepidoptera: Gelechiidae) under laboratory conditions - Shamim Akhtar; Muhammad Jalal Arif; Muhammad Dildar Gogi; Imran ul Haq (International Journal of Tropical Insect Science, 2022)

Carica papaya ameliorates thrombocytopenia through upregulation of Interleukin-11 and modulation of thrombopoietin in mouse model of carboplatin-induced myelosuppression - Sabeen Irshad; Arham Shabbir; Hina Aslam; Tasleem Akhtar; Muhammad Shahzad (Molecular Biology Reports, 2022)

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Dynamic linkages between climatic variables and agriculture production in Malaysia: a generalized method of moments approach - Rulia Akhtar; Muhammad Mehedi Masud (Environmental Science and Pollution Research, 2022)

Assessment of cobalt in wheat grains as affected by diverse fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Shahzad Akhtar; Razia Sultana; Muhammad Nadeem; Muhammad Iftikhar Hussain; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Appraising growth, daily intake, health risk index, and pollution load of Zn in wheat (Triticum aestivum L.) grown in soil differentially spiked with zinc - Abid Ejaz; Zafar Iqbal Khan; Kafeel Ahmad; Fatima Ghulam Muhammad; Shahzad Akhtar; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Static force-based seismic analysis of reinforced concrete frames having weaker beam-column joints - Naveed Ahmad; Muhammad Rizwan; Qaisar Ali; Akhtar Naeem Khan (European Journal of Environmental and Civil Engineering, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Polystichum braunii ameliorates airway inflammation by attenuation of inflammatory and oxidative stress biomarkers, and pulmonary edema by elevation of aquaporins in ovalbumin-induced allergic asthmatic mice - Ammara Saleem; Afza Mubeen; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2022)

From the COVID-19 pandemic to corrupt practices: a tale of two evils - Muhammad Usman; Mudassir Husnain; Muhammad Waheed Akhtar; Yameen Ali; Areej Riaz; Aimon Riaz (Environmental Science and Pollution Research, 2022)

Controlled nitrogen transformation in chemo-amended urea improves nitrogen use efficiency and productivity of wheat grown on alkaline calcareous soil - Arooba Ashraf; Muhammad Akhtar; Muhammad Ashraf; Saddam Hussain (Environmental Science and Pollution Research, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Evaluating pollution damage function through carbon pricing, renewable energy demand, and cleaner technologies in China: blue versus green economy - Muhammad Zaheer Akhtar; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Evaluation of nickel toxicity in wheat as function of diverse type of fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Razia Sultana; Shahzad Akhtar; Muhammad Nadeem (Environmental Science and Pollution Research, 2022)

Molecular characterization and hematological analysis of Listeria monocytogenes infection in dairy cows in Punjab (Pakistan) - Muhammad Zubair Munir; Jawaria Ali Khan; Muhammad Ijaz; Fareeha Akhtar (Archives of Microbiology, 2022)

Systematic analysis of HD-ZIP transcription factors in sesame genome and gene expression profiling of SiHD-ZIP class I entailing drought stress responses at early seedling stage - Maryam Mehmood; Muhammad Jadoon Khan; Muhammad Jawad Khan; Nadeem Akhtar; Fizza Mughal; Syed Tahir Abbas Shah; Muhammad Zeeshan Hyder; Sumaira Farrakh; Irfan Sadiq (Molecular Biology Reports, 2022)

Quantitative evaluation of zinc metal in meadows and ruminants for health assessment: implications for humans﻿ - Ayesha Maqsood; Zafar Iqbal Khan; Kafeel Ahmad; Shahzad Akhtar; Asma Ashfaq; Ifra Saleem Malik; Razia Sultana; Muhammad Nadeem; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Stimulating student’s pro-environmental behavior in higher education institutions: an ability–motivation–opportunity perspective - Sadia Akhtar; Kashif Ullah Khan; Fouzia Atlas; Muhammad Irfan (Environment, Development and Sustainability, 2022)

Effectiveness of exogenously applied chelated micronutrients for biofortification of wheat - Muhammad Imran Tipu; Muhammad Akhtar; Nadeem Sarwar; Saddam Hussain (Arabian Journal of Geosciences, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

RETRACTED ARTICLE: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

Designing Fusion Molecules from Antigens of Mycobacterium tuberculosis to Enhance Serodiagnostic Sensitivity in Latent TB Infection and Active TB State - Chandni Yaqoob; Saher Shahid; Aasia Khaliq; Zaib un Nisa; Imran H. Khan; Muhammad Waheed Akhtar (International Journal of Peptide Research and Therapeutics, 2022)

Cyperus iria aqueous-ethanol extract ameliorated hyperglycemia, oxidative stress, and regulated inflammatory cytokines in streptozotocin-induced diabetic rats - Myeda Saeed; Ali Sharif; Saeed Ul Hassan; Bushra Akhtar; Faqir Muhammad; Maryam Malik (Environmental Science and Pollution Research, 2022)

Gravity and electrical resistivity investigations to mark concealed seepage sources from Kanjoor Dam, Pakistan - Waqar Ali Zafar; Urooj Shakir; Rizwan Ahmed; Junaid Ahmed; Muhammad Younis Khan; Shamim Akhtar; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Azhar Rasul; Mirza Muhammad Faran Ashraf Baig (Natural Product Research, 2021)

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Green Synthesis of Silver Nitrate Nanoparticles from Camelina Sativa (L.) and Its Effect to Control Insect Pests of Stored Grains - Habib ur Rehman; Beenish Majeed; Muhammad Aslam Farooqi; Amer Rasul; Muhammad Sagheer; Qurban Ali; Zunnu Raen Akhtar (International Journal of Tropical Insect Science, 2021)

Comparison of individual and combination treatments with naproxen, prednisolone and hydroxychloroquine to treat Complete Freund’s Adjuvant induced arthritis - Muhammad Furqan Akhtar; Summiya Zubair; Ammara Saleem; Khalaf F. Alsharif; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Tetraconodon and Sivachoerus (Suidae) from Dhok Pathan and Hasnot area of Potwar Plateau, northern Pakistan - Muhammad Adeeb Babar; Kiran Aftab; Muhammad Akbar Khan; Sayyad Ghyour Abbas; Muhammad Asim; Muhammad Akhtar (Arabian Journal of Geosciences, 2021)

Iron-doped zinc oxide nanoparticles-triggered elicitation of important phenolic compounds in cell cultures of Fagonia indica - Atta Ullah Khan; Tariq Khan; Mubarak Ali Khan; Akhtar Nadhman; Muhammad Aasim; Nadir Zaman Khan; Waqar Ali; Nausheen Nazir; Muhammad Zahoor (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Satires, narratives and journalistic divides: Discourses on free speech in Western and Islamic news media - Muhammad Khalil Khan; Fei Wu; Cornelius B. Pratt; Nadeem Akhtar (The Social Science Journal, 2021)

High-fat diet-induced splenic, hepatic, and skeletal muscle architecture damage: cellular and molecular players - Ambreen Asghar; Tasleem Akhtar; Tayyeba Batool; Muhammad Babar Khawar; Sania Nadeem; Rabia Mehmood; Nadeem Sheikh (Molecular and Cellular Biochemistry, 2021)

Recent updates on immunological, pharmacological, and alternative approaches to combat COVID-19 - Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Haris; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Environmental impact and diversity of protease-producing bacteria in areas of leather tannery effluents of Sialkot, Pakistan - Muhammad Qasim Butt; Nadia Zeeshan; Naeem Mahmood Ashraf; Muhammad Aftab Akhtar; Hina Ashraf; Amber Afroz; Aqsa Shaheen; Shumaila Naz (Environmental Science and Pollution Research, 2021)

Nitrogen balance, production performance, and plasma metabolites of lactating buffaloes in response to varying dietary protein levels - Muhammad Uzair Akhtar; Hifzulrahman; Muhammad Imran; Talat Naseer Pasha; Anjum Khalique; Muhammad Saadullah; Muhammad Naeem Tahir; Muhammad Ikram-ul-Haq; Muhammad Naveed-ul-Haque (Tropical Animal Health and Production, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Outer Membrane Protein‐Coated Nanoparticles as Antibacterial Vaccine Candidates - Majid Anwar; Faqir Muhammad; Bushra Akhtar; Muhammad Irfan Anwar; Ahmad Raza; Abdul Aleem (International Journal of Peptide Research and Therapeutics, 2021)

Arbuscular mycorrhizal fungi improve growth, essential oil, secondary metabolism, and yield of tobacco (Nicotiana tabacum L.) under drought stress conditions - Naheeda Begum; Kashif Akhtar; Muhammad Abass Ahanger; Mudassar Iqbal; Pingping Wang; Nabil S. Mustafa; Lixin Zhang (Environmental Science and Pollution Research, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

Correction to: Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Carrageenan oligomers and salicylic acid act in tandem to escalate artemisinin production by suppressing arsenic uptake and oxidative stress in Artemisia annua (sweet wormwood) cultivated in high arsenic soil - Muhammad Naeem; Tariq Aftab; Abid Ali Ansari; Mohammad Masroor Akhtar Khan (Environmental Science and Pollution Research, 2021)

Fabrication of nickel-tagged magnetic imprinted polymeric network for the selective extraction of Ni(II) from the real aqueous samples - Sagar Kumar; Aamna Balouch; Esra Alveroğlu; Muhammad Saqaf Jagirani; Abdullah; Moina Akhtar Mughal; Dadu Mal (Environmental Science and Pollution Research, 2021)

Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Phenolic, flavonoid content and radical scavenging activity of Smilax china with its inhibitory potential against clinically important enzymes - Hafiz Ibtesam Ahmad; Haji Muhammad Shoaib Khan; Naveed Akhtar; Shakeel Ijaz (Natural Product Research, 2021)

RETRACTED ARTICLE: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2021)

Neuroprotective potential of Malva neglecta is mediated via down-regulation of cholinesterase and modulation of oxidative stress markers - Uzma Saleem; Rubina Akhtar; Fareeha Anwar; Muhammad Ajmal Shah; Zunera Chaudary; Muhammad Ayaz; Bashir Ahmad (Metabolic Brain Disease, 2021)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

Removal of N-terminal methionine of human interferon α-2b by co‐producing with Pyrococcus furiosus methionine aminopeptidase in Escherichia coli - Amina Arif; Naeem Rashid; Muhammad Akhtar (Biologia, 2021)

Effect of feeding calcium propionate supplemented cotton seed cake on milk yield, milk composition and aflatoxin concentration in lactating buffaloes - Murtaza Ali Tipu; Anjum Khalique; Muhammad Naveed-ul-Haque; Muhammad Qamer Shahid; Maqsood Akhtar; Mubashir Ilyas (Tropical Animal Health and Production, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

P53-mediated in vitro inhibition of PhIP-induced oxidative damage by myricetin bulk and nano forms in healthy lymphocytes - Shabana Akhtar; Diana Anderson; Talha Muhammad Azam; Arif Malik (Archives of Toxicology, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Chemical characterization and anti-arthritic appraisal of Monotheca buxifolia methanolic extract in Complete Freund’s Adjuvant-induced arthritis in Wistar rats - Muhammad Furqan Akhtar; Khushdil Khan; Ammara Saleem; Mirza Muhammad Faran Ashraf Baig; Azhar Rasul; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Asphodelus tenuifolius extracts arrested inflammation and arthritis through modulation of TNF-α, NF-κB, ILs, and COX-2 activities in in vivo models - Mohammad Saleem; Anam Iftikhar; Muhammad Asif; Khalid Hussain; Alamgeer; Pervaiz Akhtar Shah; Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Tanzeem; Hafiza Sidra Yaseen (Inflammopharmacology, 2021)

Correction to: Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Influence of abiotic factors on population dynamics of SOGATELLA FURCIFERA HORVATH (DELPHACIDAE: HOMOPTERA) - Ijaz Haider; Muhammad Sufyan; Muhammad Akhtar; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2021)

Treatment of Wilms’ nephroblastoma cancer cells via EGFR targeting of dactinomycin loaded DNA-nanowires - Mirza Muhammad Faran Ashraf Baig; Chengfei Zhang; Muhammad Furqan Akhtar; Ammara Saleem; Naveed Nisar (Journal of Pharmaceutical Investigation, 2021)

Temporal Analysis for Detection of Anomalies in Precipitation Patterns over a Selected Area in the Indus Basin of Pakistan - Akhtar Ali; Hafiz Umar Farid; Zahid Mehmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Muhammad Mubeen; Aamir Shakoor (Pure and Applied Geophysics, 2021)

Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Antibiofilm Effects of Macrolide Loaded Microneedle Patches: Prospects in Healing Infected Wounds - Muhammad Sohail Arshad; Aleema Tehreem Zahra; Saman Zafar; Hussain Zaman; Ambreen Akhtar; Muhammad Mazhar Ayaz; Israfil Kucuk; Mohammed Maniruzzaman; Ming-Wei Chang; Zeeshan Ahmad (Pharmaceutical Research, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

RETRACTED ARTICLE: Polystichum braunii extracts inhibit Complete Freund’s adjuvant-induced arthritis via upregulation of I-κB, IL-4, and IL-10, downregulation of COX-2, PGE2, IL-1β, IL-6, NF-κB, and TNF-α, and subsiding oxidative stress - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Oral supplementation of Ficus religiosa leaf extract adversely affects the selected behavioral aspects of male albino mice - Naheed Akhtar; Shahid Iqbal; Muhammad Faisal Shahzad; Muhammad Latif; Furhan Iqbal (Biologia, 2020)

The comparative analysis of essential nutrient fractions in permafrost and different land use systems of Diamer Division, Gilgit-Baltistan - Didar Ahmad; Farhan Hafeez; Muhammad Irshad; Qaisar Mehmood; Adnan Ahmed Tahir; Akhtar Iqbal; Faridullah (Arabian Journal of Geosciences, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Soil selenium transformation across different parent materials in Pothwar uplands of Pakistan - Muhammad Imran; Mohammad Saleem Akhtar; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Chen Zhikun; Ghulam Mujtaba (Arabian Journal of Geosciences, 2020)

Attenuating the adverse aspects of water stress on wheat genotypes by foliar spray of melatonin and indole-3-acetic acid - Sara Zafar; Muhammad Akhtar; Shagufta Perveen; Zuhair Hasnain; Aansa Khalil (Physiology and Molecular Biology of Plants, 2020)

Changes in Soil Organic Carbon Fractions Across a Loess Toposequence - Arsalan Azam; Mohammad Saleem Akhtar; Shah Rukh; Ayaz Mehmood; Muhammad Imran; Ahmad Khan; Abdul Qayyum; Waseem Ahmad; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2020)

Development of green methodologies for Heck, Chan–Lam, Stille and Suzuki cross-coupling reactions - Muhammad Yousaf; Ameer Fawad Zahoor; Rabia Akhtar; Matloob Ahmad; Shazia Naheed (Molecular Diversity, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

A novel nonsense mutation in NPR2 gene causing Acromesomelic dysplasia, type Maroteaux in a consanguineous family in Southern Punjab (Pakistan) - Saima Mustafa; Zafrin Akhtar; Muhammad Latif; Mubashir Hassan; Muhammad Faisal; Furhan Iqbal (Genes & Genomics, 2020)
Background Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia following autosomal recessive mode of inheritance and characterized by abnormal growth plates, short and abnormal bones in the extremities and spine. Objective Present study was designed to report the molecular basis of AMDM in enrolled consanguineous family from Pakistan. Methods A consanguineous family from Vehari District in Pakistan having multiple siblings suffering from AMDM was enrolled in present study. Whole exome sequencing (WES) approach was adopted to identify causative agent of AMDM. Human full length NPR2 gene and sequence with nonsense mutation was amplified by using Myc-tagged pXN vector and transformed in E. coli DH5α cells to confirm mutation. SDS-PAGE and Western blotting were done to confirm the production of truncated protein. Computational three dimensional structure generation through homology modeling approach was done to compare protein structure between patients and controls. Results WES reveled a nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene leading to premature termination codon in mRNA of NPR2 gene resulting in a truncated protein with 204 amino acid residues that was confirmed by SDS-PAGE and Western blotting. Sanger sequencing confirmed that mutation in all subjects and mutation followed Mendalian pattern of inheritance. Multiple sequence alignment by ClustalW revealed that mutated domain of NPR2 is conserved region. Proetin structure comparison revealed a significant structural part of NPR2 was missing in truncated protein as compared to control. Conclusion We are reporting that a novel nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene is causing AMDM in a consanguineous Pakistani family.

Vibration analysis of damaged and undamaged steel structure systems: cantilever column and frame - Muhammad Abuzar Khan; Kareem Akhtar; Naveed Ahmad; Feroz Shah; Naeem Khattak (Earthquake Engineering and Engineering Vibration, 2020)

Systematic and paleoecological study of the new remains of Brachypotherium (Rhinocerotidae) from the Middle Miocene Siwaliks (Pakistan) - Amtur Rafeh; Abdul Majid Khan; Rana Manzoor Ahmad; Mudassar Iqbal; Muhammad Akhtar (Arabian Journal of Geosciences, 2020)

Lipospheres for Simultaneous Controlled Release and Improved Pharmacokinetic Profiles of Saxagliptin-Enalapril: Formulation, Optimization, and Comparative In Vitro-In Vivo Evaluation - Safirah Maheen; Akhtar Rasul; Muhammad Hanif; Hafeez Ullah Khan (AAPS PharmSciTech, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

RETRACTED ARTICLE: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

Hazards of nitrogen fertilizers and ways to reduce nitrate accumulation in crop plants - Moddassir Ahmed; Muhammad Rauf; Muhammad Akhtar; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Nephroprotective effects of curcumin loaded chitosan nanoparticles in cypermethrin induced renal toxicity in rabbits - Maira Anwar; Faqir Muhammad; Bushra Akhtar; Sajjad ur Rehman; Muhammad Kashif Saleemi (Environmental Science and Pollution Research, 2020)

On the asymmetric effects of premature deindustrialization on CO2 emissions: evidence from Pakistan - Sana Ullah; Ilhan Ozturk; Ahmed Usman; Muhammad Tariq Majeed; Parveen Akhtar (Environmental Science and Pollution Research, 2020)

Oxidative stress risk assessment through heavy metal and arsenic exposure in terrestrial and aquatic bird species of Pakistan - Shamsa Kanwal; Naeem Akhtar Abbasi; Muhammad Jamshed Iqbal Chaudhry; Sajid Rashid Ahmad; Riffat Naseem Malik (Environmental Science and Pollution Research, 2020)

Ammonia inhalation-induced inflammation and structural impairment in the bursa of fabricius and thymus of broilers through NF-κB signaling pathway - Syed Waqas Ali Shah; Muhammad Ishfaq; Muhammad Nasrullah; Abdul Qayum; Muhammad Usman Akhtar; Hyeonsoo Jo; Muhammad Hussain; Xiaohua Teng (Environmental Science and Pollution Research, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Correction to: Moringa oleifera leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Moringa rivae leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

Structural styles, hydrocarbon prospects, and potential of Miano and Kadanwari fields, Central Indus Basin, Pakistan - Saif-Ur-Rehman K. Jadoon; Ding Lin; Siddique Akhtar Ehsan; Ishtiaq A. K. Jadoon; Muhammad Idrees (Arabian Journal of Geosciences, 2020)

Characterization of tomato mosaic virus and search for its resistance in Solanum species - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Mudasser Habib (European Journal of Plant Pathology, 2019)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

First report of molecular characterization of Aspergillus flavus from maize in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Syed Wajih ul Hassan; Muhammad Rafique Asi; Yumna Sadef (Journal of Plant Pathology, 2019)

Evaluation of tomato genotypes for early blight disease resistance caused by Alternaria solani in Pakistan - Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Yussouf Saleem; Qumer Iqbal; Muhammad Asghar; Abdul Rehman Khan (Journal of Plant Pathology, 2019)

Phosphate fertilizer premixing with farmyard manure enhances phosphorus availability in calcareous soil for higher wheat productivity - Wasiq Ikram; Muhammad Akhtar; Christian Morel; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Zinc biofortification of cereals—role of phosphorus and other impediments in alkaline calcareous soils - Muhammad Akhtar; Sundas Yousaf; Nadeem Sarwar; Saddam Hussain (Environmental Geochemistry and Health, 2019)

Comparative Analysis of Draft Genome Sequence of Rhodococcus sp. Eu-32 with Other Rhodococcus Species for Its Taxonomic Status and Sulfur Metabolism Potential - Nasrin Akhtar; Muhammad A. Ghauri; Kalsoom Akhtar; Sana Parveen; Muhammad Farooq; Aamir Ali; Peter Schierack (Current Microbiology, 2019)

Variability in the immunogenic preS region of Pakistani hepatitis B virus isolates - Saima Iftikhar; Muhammad Akhtar (VirusDisease, 2019)

First report of cucumber mosaic virus subgroup IB and II isolates infecting tomatoes in Pakistan - Marium Anwer; Khalid P. Akhtar; Najeeb Ullah; Muhammad Y. Saleem; Hafiza Massoma Naseer Cheema (Journal of Plant Pathology, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

Physiological and biochemical attributes of bread wheat (Triticum aestivum L.) seedlings are influenced by foliar application of silicon and selenium under water deficit - Abdul Sattar; Mumtaz Akhtar Cheema; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Ahmad Nawaz; Tahira Abbas; Qasim Ali (Acta Physiologiae Plantarum, 2019)

Evaluation of Abuse-Deterrent Characteristics of Tablets Prepared via Hot-Melt Extrusion - Xiaoming Xu; Akhtar Siddiqui; Charudharshini Srinivasan; Adil Mohammad; Ziyaur Rahman; Maxwell Korang-Yeboah; Xin Feng; Mansoor Khan; Muhammad Ashraf (AAPS PharmSciTech, 2019)

The role of selenium on mitigating arsenic accumulation, enhancing growth and antioxidant responses in metallicolous and non-metallicolous population of Isatis cappadocica Desv. and Brassica oleracea L - Naser Karimi; Fariba Vakilipak; Zahra Souri; Muhammad Ansar Farooq; Javaid Akhtar (Environmental Science and Pollution Research, 2019)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

A contingent valuation approach to evaluating willingness to pay for an improved water pollution management system in Dhaka City, Bangladesh - Farhana Sehreen; Muhammad Mehedi Masud; Rulia Akhtar; Md. Razu Ahmad Masum (Environmental Monitoring and Assessment, 2019)

Haunch retrofitting technique for seismic upgrading deficient RC frames - Naveed Ahmad; Junaid Akbar; Muhammad Rizwan; Bashir Alam; Akhtar Naeem Khan; Abdul Lateef (Bulletin of Earthquake Engineering, 2019)

Removal of pirimicarb from agricultural waste water using cellulose acetate–modified ionic liquid membrane - Sana Zulfiqar; Uzaira Rafique; Muhammad Javed Akhtar (Environmental Science and Pollution Research, 2019)

First report of Macrophomina phaseolina causing dry root rot of lentil in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Jawad Asghar; Ghulam Abbas (Journal of Plant Pathology, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

Petrology and geochemistry of dolerite and lamprophyre sills in Mesozoic successions of Khanozai–Muslim Bagh area, northwestern Pakistan - Din Muhammad; Razzaq Abdul Manan Durrani; Akhtar Muhammad Kassi; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2019)

pH/Thermo-Dual Responsive Tunable In Situ Cross-Linkable Depot Injectable Hydrogels Based on Poly(N-Isopropylacrylamide)/Carboxymethyl Chitosan with Potential of Controlled Localized and Systemic Drug Delivery - Samiullah Khan; Naveed Akhtar; Muhammad Usman Minhas; Syed Faisal Badshah (AAPS PharmSciTech, 2019)

Chemical characterisation and hepatoprotective potential of Cosmos sulphureus Cav. and Cosmos bipinnatus Cav. - Mohammad Saleem; Hafiz Akbar Ali; Muhammad Furqan Akhtar; Uzma Saleem; Ammara Saleem; Iram Irshad (Natural Product Research, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Endocrine disruption as an adverse effect of non-endocrine targeting pharmaceuticals - Shakila Sabir; Muhammad Furqan Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2019)

Extremely stable indole-3-glycerol-phosphate synthase from hyperthermophilic archaeon Pyrococcus furiosus - Muhammad Arif; Naeem Rashid; Sumera Perveen; Qamar Bashir; Muhammad Akhtar (Extremophiles, 2019)

Redox balance and DNA fragmentation in arsenic-exposed occupational workers from different industries of Pakistan - Maryam Raza; Ishrat Mahjabeen; Muhammad Fahim; Waqar Ahmad Malik; Asad Ullah Khan; Mahmood Akhtar Kayani; Ayesha Khan; Zertashia Akram (Environmental Science and Pollution Research, 2018)

Seismic fragility functions for code compliant and non-compliant RC SMRF structures in Pakistan - Naveed Ahmad; Asif Shahzad; Qaisar Ali; Muhammad Rizwan; Akhtar Naeem Khan (Bulletin of Earthquake Engineering, 2018)

Silicon-mediated growth and yield improvement of sunflower (Helianthus annus L.) subjected to brackish water stress - Syed Azhar Hussain; Muhammad Ansar Farooq; Javaid Akhtar; Zulfiqar Ahmad Saqib (Acta Physiologiae Plantarum, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Influence of composted poultry manure and irrigation regimes on some morpho-physiology parameters of maize under semiarid environments - Wajid Farhad; Mumtaz Akhtar Cheema; Hafiz Mohkum Hammad; Muhammad Farrukh Saleem; Shah Fahad; Farhat Abbas; Ikramullah Khosa; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Phytochemical screening and in-vitro evaluation of pharmacological activities of peels of Musa sapientum and Carica papaya fruit - Sarmad Siddique; Shamsa Nawaz; Faqir Muhammad; Bushra Akhtar; Bilal Aslam (Natural Product Research, 2018)

Effects of increasing dietary protein supplies on milk yield, milk composition, and nitrogen use efficiency in lactating buffalo - Muhammad Naveed-ul-Haque; Muhammad Uzair Akhtar; Rizwan Munnawar; Saba Anwar; Anjum Khalique; Murtaza Ali Tipu; Fayyaz Ahmad; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2018)

Correction to: Pre-existing Small Vessel Disease in Patients with Acute Stroke from the Middle East, Southeast Asia, and Philippines - Naveed Akhtar; Abdul Salam; Saadat Kamran; Atlantic D’Souza; Yahia Imam; Pablo Garcia Bermejo; Muhammad Faisal Wadiwala; Ahmed Own; Ahmed ElSotouhy; Surjith Vattoth; Paula Bourke; Zain Bhutta; et al. (Translational Stroke Research, 2018)

Identification of Hydrocarbon Potential of Talhar Shale: Member of Lower Goru Formation Using Well Logs Derived Parameters, Southern Lower Indus Basin, Pakistan - Muhsan Ehsan; Hanming Gu; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Zaheen Ullah (Journal of Earth Science, 2018)

Biodesulfurization of Thiophenic Compounds by a 2-Hydroxybiphenyl-Resistant Gordonia sp. HS126-4N Carrying dszABC Genes - Nasrin Akhtar; Kalsoom Akhtar; Muhammad A. Ghauri (Current Microbiology, 2018)

A novel Salvialactomine from the callus culture of Salvia santolinifolia Boiss - Tour Jan; Raiha Qadri; Beena Naqvi; Achyut Adhikari; Said Nadeem; Akhtar Muhammad (Natural Product Research, 2018)

Effects of nickel toxicity on morphological and physiological aspects of osmoregulation in Typha domingensis (Typhaceae) populations - Noreen Akhtar; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Khawaja Shafique Ahmad; Jiabin Deng; Ansar Mehmood; Claudia Segovia-Salcedo; Muhammad Muslim Shahnaz; Abdul Qadir Khan (Limnology, 2018)

Determination of the role of salicylic acid and Benzothiadiazole on physico-chemical alterations caused by Cucumber mosaic virus in tomato - Rana M. Sabir Tariq; Khalid P. Akhtar; Amjad Hameed; Najeeb Ullah; Muhammad Y. Saleem; Imran ul Haq (European Journal of Plant Pathology, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

Enhancement of gene expression in Escherichia coli and characterization of highly stable ATP-dependent glucokinase from Pyrobaculum calidifontis - Tahira Bibi; Musadiq Ali; Naeem Rashid; Majida Atta Muhammad; Muhammad Akhtar (Extremophiles, 2018)

Evaluation of immunostimulatory and immunotherapeutic effects of tropical mushroom (Lentinus edodes) against eimeriasis in chicken - Muhammad Irfan Ullah; Masood Akhtar; Mian Muhammad Awais; Muhammad Irfan Anwar; Kashfa Khaliq (Tropical Animal Health and Production, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

A novel trifunctional, family GH10 enzyme from Acidothermus cellulolyticus 11B, exhibiting endo-xylanase, arabinofuranosidase and acetyl xylan esterase activities - Saher Shahid; Razia Tajwar; Muhammad Waheed Akhtar (Extremophiles, 2018)

Application of Optical Coherence Tomography Freeze-Drying Microscopy for Designing Lyophilization Process and Its Impact on Process Efficiency and Product Quality - Maxwell Korang-Yeboah; Charudharshini Srinivasan; Akhtar Siddiqui; David Awotwe-Otoo; Celia N. Cruz; Ashraf Muhammad (AAPS PharmSciTech, 2018)

Combined Applications of Aminoethoxyvinylglycine with Salicylic Acid or Nitric Oxide Reduce Oxidative Stress in Peach During Ripening and Cold Storage - Mohammad Javed Tareen; Zora Singh; Ahmad Sattar Khan; Nadeem Akhtar Abbasi; Muhammad Naveed (Journal of Plant Growth Regulation, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Phosphate-arsenate relations to affect arsenic concentration in plant tissues, growth, and antioxidant efficiency of sunflower (Helianthus annuus L.) under arsenic stress - Waqas Azeem; Muhammad Ashraf; Sher Muhammad Shahzad; Muhammad Imtiaz; Mumtaz Akhtar; Muhammad Shahid Rizwan (Environmental Science and Pollution Research, 2017)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Pcal_1311, an alcohol dehydrogenase homologue from Pyrobaculum calidifontis, displays NADH-dependent high aldehyde reductase activity - Raza Ashraf; Naeem Rashid; Tamotsu Kanai; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Postpartum endocrine activities, metabolic attributes and milk yield are influenced by thermal stress in crossbred dairy cows - Ihsanullah; Muhammad Subhan Qureshi; Syed Muhammad Suhail; Sohail Akhtar; Rifat Ullah Khan (International Journal of Biometeorology, 2017)

Pb-induced changes in roots of two cultivated rice cultivars grown in lead-contaminated soil mediated by smoke - Nazneen Akhtar; Sehresh Khan; Ijaz Malook; Shafiq Ur Rehman; Muhammad Jamil (Environmental Science and Pollution Research, 2017)

Variants in the PRPF8 Gene are Associated with Glaucoma - Shazia Micheal; Barend F. Hogewind; Muhammad Imran Khan; Sorath Noorani Siddiqui; Saemah Nuzhat Zafar; Farah Akhtar; Raheel Qamar; Carel B. Hoyng; Anneke I. den Hollander (Molecular Neurobiology, 2017)

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

Structural and functional characteristics of plant proteinase inhibitor-II (PI-II) family - Shazia Rehman; Ejaz Aziz; Wasim Akhtar; Muhammad Ilyas; Tariq Mahmood (Biotechnology Letters, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

Petrology and provenance of the Neogene fluvial succession in Pishin Belt (Katawaz Basin) western Pakistan: implications for sedimentation in peripheral forelands basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Razzaq Abdul Manan (Geosciences Journal, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Equilibrium modeling of cadmium biosorption from aqueous solution by compost - Iftikhar Ahmad; Muhammad Javed Akhtar; Iram Bashir Khan Jadoon; Muhammad Imran; Muhammad Imran; Shahid Ali (Environmental Science and Pollution Research, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

The knowledge, awareness, attitude and motivational analysis of plastic waste and household perspective in Malaysia - Rafia Afroz; Ataur Rahman; Muhammad Mehedi Masud; Rulia Akhtar (Environmental Science and Pollution Research, 2017)

Synthesis, biological activities and docking studies of novel 2,4-dihydroxybenzaldehyde based Schiff base - Shahzad Murtaza; Aadil Abbas; Kiran Iftikhar; Saima Shamim; Muhammad Shoaib Akhtar; Zobia Razzaq; Khadija Naseem; Abdallah Mohamed Elgorban (Medicinal Chemistry Research, 2016)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Analysis of geological structure and anthropological factors affecting arsenic distribution in the Lahore aquifer, Pakistan - Akhtar Malik Muhammad; Tang Zhonghua; Zakari Sissou; Bahaa Mohamadi; Muhsan Ehsan (Hydrogeology Journal, 2016)

Pcal_1127, a highly stable and efficient ribose-5-phosphate pyrophosphokinase from Pyrobaculum calidifontis - Tahira Bibi; Sumera Perveen; Iram Aziz; Qamar Bashir; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

A new fatty acid ester from an edible mushroom Rhizopogon luteolus - Gülsen Tel-Çayan; Akhtar Muhammad; Mehmet Emin Duru; Mehmet Öztürk; Achyut Adhikari; Aziz Türkoğlu (Natural Product Research, 2016)

Biotransformation of Tetrahydrocannabinol - Muhammad T. Akhtar; Khozirah Shaari; Robert Verpoorte (Phytochemistry Reviews, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Erratum to: Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobaculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Dibenzothiophene desulfurization capability and evolutionary divergence of newly isolated bacteria - Nasrin Akhtar; Muhammad A. Ghauri; Kalsoom Akhtar (Archives of Microbiology, 2016)

Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobacculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake - Iftikhar Ahmad; Muhammad Javed Akhtar; Hafiz Naeem Asghar; Umber Ghafoor; Muhammad Shahid (Journal of Plant Growth Regulation, 2016)

Differential accumulation of potassium results in varied salt-tolerance response in tomato (Solanum lycopersicum L.) cultivars - Muhammad Amjad; Javaid Akhtar; Behzad Murtaza; Ghulam Abbas; Husnain Jawad (Horticulture, Environment, and Biotechnology, 2016)

Detrital mode and whole-rock geochemistry of the Miocene-Pliocene fluvial succession, Pishin Belt, Pakistan: implications on provenance and source area weathering in peripheral foreland basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Muhammad Umar; Mohibullah Mohibullah; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2016)

Relationship between rhizosphere acidification and phytoremediation in two acacia species - Ghulam Abbas; Muhammad Saqib; Javaid Akhtar; Ghulam Murtaza; Muhammad Shahid; Amjad Hussain (Journal of Soils and Sediments, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Morpho-anatomical and physiological adaptations to high altitude in some Aveneae grasses from Neelum Valley, Western Himalayan Kashmir - Khawaja Shafique Ahmad; Mansoor Hameed; Sana Fatima; Muhammad Ashraf; Farooq Ahmad; Mehwish Naseer; Noreen Akhtar (Acta Physiologiae Plantarum, 2016)

Therapeutic Efficacy of Neurostimulation for Depression: Techniques, Current Modalities, and Future Challenges - Hafsah Akhtar; Faiza Bukhari; Misbah Nazir; Muhammad Nabeel Anwar; Adeeb Shahzad (Neuroscience Bulletin, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Pcal_1699, an extremely thermostable malate dehydrogenase from hyperthermophilic archaeon Pyrobaculum calidifontis - Ghazaleh Gharib; Naeem Rashid; Qamar Bashir; Qura-tul Ann Afza Gardner; Muhammad Akhtar; Tadayuki Imanaka (Extremophiles, 2016)

Reservoir attributes of a hydrocarbon-prone sandstone complex: case of the Pab Formation (Late Cretaceous) of Southwest Pakistan - Muhammad Umar; Abdul Salam Khan; Gilbert Kelling; Henrik Friis; Akhtar Muhammad Kassi (Arabian Journal of Geosciences, 2016)

Prevalence and distribution of human Plasmodium infection in Federally Administrative Tribal Areas of Pakistan - Irfan Hussain; Naveeda Akhtar Qureshi; Muhammad Afzal; Nargis Shaheen; Abid Ali; Asma Ashraf (Acta Parasitologica, 2016)
About 3.6 million Pashtun and over 1.5 million immigrants from Afghanistan live in the federally administered tribal areas (FATA) on the border between Pakistan’s Khyber Pakhtunkhwa Province and southern Afghanistan. Although malaria cases are common in FATA, no detailed studies have yet been performed to reveal the actual status of malaria in the local population and epidemiological data are insufficient to elucidate the actual incidence. A malariometric survey of 691 patients of all ages and genders in seven agencies (districts) in FATA was carried out in 2013 using whole blood samples. Microscopically confirmed positive species were subjected to nested-PCR for the reconfirmation and detection of four species of

Effect of ethylene glycol dimethacrylate on swelling and on metformin hydrochloride release behavior of chemically crosslinked pH–sensitive acrylic acid–polyvinyl alcohol hydrogel - Muhammad Faheem Akhtar; Nazar Muhammad Ranjha; Muhammad Hanif (DARU Journal of Pharmaceutical Sciences, 2015)

New fossil remains of family Cervidae from the Dhok Pathan Formation (Middle Siwaliks) of Pakistan - Abdul Ghaffar; Muhammad Akhtar; Muhammad Akbar Khan; Muhammad Khaled Siddiq (Geosciences Journal, 2015)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Consumer purchase intention towards environmentally friendly vehicles: an empirical investigation in Kuala Lumpur, Malaysia - Rafia Afroz; Muhammad Mehedi Masud; Rulia Akhtar; Md. Ashraful Islam; Jarita Bt Duasa (Environmental Science and Pollution Research, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Production of human interferon alpha-2b in Escherichia coli and removal of N-terminal methionine utilizing archaeal methionine aminopeptidase - Amina Arif; Qura-Tul-Ann A. Gardner; Naeem Rashid; Muhammad Akhtar (Biologia, 2015)

Exploring factors influencing farmers’ willingness to pay (WTP) for a planned adaptation programme to address climatic issues in agricultural sectors - Adeel Ahmed; Muhammad Mehedi Masud; Abul Quasem Al-Amin; Siti Rohani Binti Yahaya; Mahfuzur Rahman; Rulia Akhtar (Environmental Science and Pollution Research, 2015)

Phylogenetic characterization and novelty of organic sulphur metabolizing genes of Rhodococcus spp. (Eu-32) - Nasrin Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Shaun Heaphy (Biotechnology Letters, 2015)

Pro-environmental behavior and public understanding of climate change - Muhammad Mehedi Masud; Rulia Akhtar; Rafia Afroz; Abul Quasem Al-Amin; Fatimah Binti Kari (Mitigation and Adaptation Strategies for Global Change, 2015)

mRNA secondary structure engineering of Thermobifida fusca endoglucanase (Cel6A) for enhanced expression in Escherichia coli - Imran Ali; Rehana Asghar; Sajjad Ahmed; Muhammad Sajjad; Muhammad Tariq; M. Waheed Akhtar (World Journal of Microbiology and Biotechnology, 2015)

Estimating farmers’ willingness to pay for climate change adaptation: the case of the Malaysian agricultural sector - Muhammad Mehedi Masud; Ha Junsheng; Rulia Akhtar; Abul Quasem Al-Amin; Fatimah Binti Kari (Environmental Monitoring and Assessment, 2015)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Genetic analysis of post-weaning growth traits of Thalli sheep under tropical conditions - Asghar Hussain; Pervez Akhtar; Safdar Ali; Khalid Javed; Muhammad Younas; Abdul Shakoor; Usman Waheed (Tropical Animal Health and Production, 2014)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

Cadmium-tolerant bacteria induce metal stress tolerance in cereals - Iftikhar Ahmad; Muhammad Javed Akhtar; Zahir Ahmad Zahir; Muhammad Naveed; Birgit Mitter; Angela Sessitsch (Environmental Science and Pollution Research, 2014)

An analysis of the resistance of Gossypium arboreum to cotton leaf curl disease by grafting - Rahim Ullah; Khalid P. Akhtar; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Directed Evolution of Clostridium phytofermentans Glycoside Hydrolase Family 9 Endoglucanase for Enhanced Specific Activity on Solid Cellulosic Substrate - Sajjad Ahmad; Hui Ma; Muhammad Waheed Akhtar; Yi-Heng Percival Zhang; Xiao-Zhou Zhang (BioEnergy Research, 2014)

Characteristics, modification and environmental application of Yemen’s natural bentonite - Aref Alshameri; Alkhafaji R.Abood; Chunjie Yan; Akhtar Malik Muhammad (Arabian Journal of Geosciences, 2014)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

Salinity and drought interaction in wheat (Triticum aestivum L.) is affected by the genotype and plant growth stage - Muhammad Saqib; Javaid Akhtar; Ghulam Abbas; Muhammad Nasim (Acta Physiologiae Plantarum, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

Rb1/105 gene alterations and head and neck carcinogenesis - Maimoona Sabir; Ruqia Mehmood Baig; Ishrat Mahjabeen; Muhammad Saeed; Faraz Arshad Malik; Mahmood Akhtar Kayani (Molecular Biology Reports, 2012)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Seasonal prevalence of coccidiosis in industrial broiler chickens in Faisalabad, Punjab, Pakistan - Mian Muhammad Awais; Masood Akhtar; Zafar Iqbal; Faqir Muhammad; Muhammad Irfan Anwar (Tropical Animal Health and Production, 2012)

DNA typing of Pakistani cattle breeds Tharparkar and Red Sindhi by microsatellite markers - Amber Azam; Masroor Ellahi Babar; Sehrish Firyal; Aftab Ahmad Anjum; Nabeela Akhtar; Muhammad Asif; Tanveer Hussain (Molecular Biology Reports, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

Effect of Mineral Fortification on Plasma Biochemical Profile in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; Munammad Tauseef Sultan; Muhammad Riaz; Anwaar Ahmed (Biological Trace Element Research, 2011)

First cloning and characterization of aspartate aminotransferase from river buffalo (Bubalus bubalis) - Muhammad Shahid Nadeem; Naeem Rashid; Muzaffar Iqbal; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Granzyme M: characterization with sites of post-translational modification and specific sites of interaction with substrates and inhibitors - Rukhshan Khurshid; Mahjabeen Saleem; Muhammad Saleem Akhtar; Asmat Salim (Molecular Biology Reports, 2011)

Gene cloning and characterization of glycine oxidase from newly isolated Bacillus subtilis strain R5 - Farrukh Jamil; Naeem Rashid; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Resistance of Solanum species to Cucumber mosaic virus subgroup IA and its vector Myzus persicae - Khalid Pervaiz Akhtar; Muhmmad Yussouf Saleem; Muhammad Asghar; Mushtaq Ahmad; Nighat Sarwar (European Journal of Plant Pathology, 2010)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

Correlative evidence for peroxidase involvement in disease resistance against Alternaria leaf blight of tomato - Amjad Hameed; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Muhammad Asghar (Acta Physiologiae Plantarum, 2010)

GIS-based high-resolution spatial interpolation of precipitation in mountain–plain areas of Upper Pakistan for regional climate change impact studies - Muhammad Waseem Ashiq; Chuanyan Zhao; Jian Ni; Muhammad Akhtar (Theoretical and Applied Climatology, 2010)

Effect of induced pyrexia on the disposition kinetics of ciprofloxacin in dogs - Faqir Muhammad; Masood Akhtar; M. Irfan Anwar; M. Javed Arshed (Veterinary Research Communications, 2009)

Seroprevalence of Toxoplasma gondii in sheep and goats in Rahim Yar Khan (Punjab), Pakistan - M. Ramzan; M. Akhtar; F. Muhammad; I. Hussain; E. Hiszczyńska-Sawicka; A. U. Haq; M. S. Mahmood; M. A. Hafeez (Tropical Animal Health and Production, 2009)

Insoluble but enzymatically active α-amylase from Bacillus licheniformis - Naeem Rashid; Alia Farooq; Ikram-ul-Haq; Muhammad Akhtar (Biologia, 2009)

Production and characterization of a highly active cellobiase from Aspergillus niger grown in solid state fermentation - Muhammad Ibrahim Rajoka; Muhammad Waheed Akhtar; Atif Hanif; A. M. Khalid (World Journal of Microbiology and Biotechnology, 2006)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)

Nitrogen transport and transformation in packed soil columns from paddy fields - Hideo Nakasone; Muhammad Akhtar Abbas; Hisao Kuroda (Paddy and Water Environment, 2004)

Optimum design of sedimentation tanks based on setting characteristics of Karachi tannery wastes - Waseem Akhtar; Muhammad Rauf; Iqbal Ali; Nayeemuddin (Water, Air, & Soil Pollution, 1997)

OPTIMUM DESIGN OF SEDIMENTATION TANKS BASED ON SETTLING CHARACTERISTICS OF KARACHI TANNERY WASTES - Waseem Akhtar; Muhammad Rauf; Iqbal Ali; Nayeemuddin (Water, Air, & Soil Pollution, 1997)